Resin composition

By using a resin composition of a specific composition, the problems of slow thickening speed and lack of adhesion in the existing resin composition are solved, and the effect of rapid thickening and maintaining adhesion at room temperature is achieved, which is suitable for the manufacture of seamless liners.

CN120209513APending Publication Date: 2025-06-27RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411936673.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-27
Filing Date
2024-12-26
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The existing resin compositions are slow to thicken at room temperature and lack adhesion after thickening, so they cannot be effectively used in the manufacture of seamless liners.

Method used

A resin composition is used which comprises a vinyl ester resin, a resin containing an ethylenically unsaturated group, a monomer with an ethylenically unsaturated group, a compound of a specific oxide and a hydroxide, and a water and a hydroxyl-containing compound. The composition thickens at room temperature at appropriate rates over time and becomes adhesive after thickening.

Benefits of technology

Fast and uniform thickening at room temperature and good adhesion after thickening is achieved, making the resin composition suitable for the manufacture of seamless liners.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211670950000251
    Figure BDA0005211670950000251
  • Figure BDA0005211670950000261
    Figure BDA0005211670950000261
  • Figure BDA0005211670950000271
    Figure BDA0005211670950000271
Patent Text Reader

Abstract

The present invention addresses the problem of providing a resin composition that thickens at a suitable rate over time at room temperature and that has adhesiveness after thickening. [Solution] A resin composition containing a vinyl ester resin (A), a resin (B) containing an ethylenically unsaturated group, a monomer (C) containing an ethylenically unsaturated group, at least one compound (D) selected from the group consisting of an oxide of a group 2 element and a hydroxide of a group 2 element, and at least one compound (E) selected from the group consisting of water and a hydroxyl group-containing compound, the vinyl ester resin (A) has a weight-average molecular weight (Mw) of 6,000 or more and a ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of 2.0 or more, and the ethylenically unsaturated group-containing resin (B) is at least one selected from the group consisting of vinyl ester resins (B1) having a carboxyl group and a weight-average molecular weight (Mw) of less than 6,000 and unsaturated polyester resins (B2) having a carboxyl group and a weight-average molecular weight (Mw) of less than 6,000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition. Background Art

[0002] In recent years, the aging of existing pipes such as water supply pipes, sewer pipes, and power pipes buried underground has become serious, and various methods for repairing them have been proposed.

[0003] For example, Patent Document 1 discloses a method for repairing an existing pipe, which includes a curing step: a tubular lining member is brought into close contact with the inner wall surface of an existing pipe buried underground, compressed air is supplied to the inside of the lining member, and at the same time, light is irradiated onto the inner surface of the lining member by a mobile light irradiation device introduced into the inside of the lining member to cure the lining member. In addition, it is described that as the material of the lining member, a material obtained by impregnating an impregnating base material containing fibers or the like with a photocurable resin composition can be used, and as the photocurable resin composition, a composition obtained by dissolving a polymerizable resin such as an unsaturated polyester resin or a vinyl ester resin in a solvent such as styrene can be used.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2020-82408 Summary of the Invention

[0007] Problems to be Solved by the Invention

[0008] A seamless lining member for pipe regeneration is manufactured as follows: a resin composition containing magnesium oxide or the like is impregnated into a base material containing glass fibers or the like, and thickened to such an extent that the resin composition can be maintained in a state of being uniformly distributed and held in the base material, and then the base material is wound into a spiral shape to be manufactured as a tubular lining member. The tubular lining member formed into a tube shape descends vertically from a high place and is folded and stored. At this time, if the adhesiveness of the overlapping portion of the base material impregnated with the resin composition is insufficient, the tube shape cannot be maintained and it cannot be used for pipe regeneration purposes.

[0009] Although the resin composition containing a vinyl ester resin used in conventional lining members is thickened by containing magnesium oxide, the thickened resin composition does not have adhesiveness, and thus there is a problem that it cannot be applied to seamless lining members.

[0010] The present invention has been completed under such circumstances, and an object thereof is to provide a resin composition that thickens at an appropriate rate over time at room temperature and has adhesiveness after thickening.

[0011] Means for Solving the Problems

[0012] That is, the present invention provides the following means.

[0013] [1] A resin composition comprising: a vinyl ester resin (A), a resin (B) containing an ethylenically unsaturated group, a monomer (C) containing an ethylenically unsaturated group, at least one compound (D) selected from oxides of Group 2 elements and hydroxides of Group 2 elements, and at least one compound (E) selected from water and compounds containing a hydroxyl group, wherein the weight-average molecular weight Mw of the vinyl ester resin (A) is 6,000 or more, and the ratio Mw / Mn of the weight-average molecular weight Mw to the number-average molecular weight Mn is 2.0 or more, and the resin (B) containing an ethylenically unsaturated group is at least one selected from a vinyl ester resin (B1) having a carboxyl group and a weight-average molecular weight Mw of less than 6,000, and an unsaturated polyester resin (B2) having a carboxyl group and a weight-average molecular weight Mw of less than 6,000.

[0014] [2] The resin composition according to the above [1], containing 50 to 70% by mass of the vinyl ester resin (A) and 30 to 50% by mass of the resin (B) containing an ethylenically unsaturated group, based on the total 100% by mass of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group.

[0015] [3] The resin composition according to the above [1] or [2], wherein the weight-average molecular weight Mw of the vinyl ester resin (A) is 35,000 or less.

[0016] [4] The resin composition according to any one of the above [1] to [3], wherein the weight-average molecular weight Mw of the vinyl ester resin (A) is 15,000 or less.

[0017] [5] The resin composition according to any one of the above [1] to [4], wherein the weight-average molecular weight Mw of the vinyl ester resin (B1) is 2,000 or more.

[0018] [6] The resin composition according to any one of the above [1] to [5], wherein the weight-average molecular weight Mw of the vinyl ester resin (B1) is 3,000 to 5,000.

[0019] [7] The resin composition according to any one of the above [1] to [6], wherein the weight-average molecular weight Mw of the unsaturated polyester resin (B2) is 1,000 to 10,000.

[0020] [8] The resin composition according to any one of [1] to [7] above, wherein the vinyl ester resin (A) is a vinyl ester resin (A1) which is an addition reaction product of a resin precursor (P1) and a polyanhydride (a-4), and the resin precursor (P1) is a reaction product of an epoxy compound (a-1) having two epoxy groups in one molecule, an unsaturated monocarboxylic acid (a-2) and a polyanhydride (a-3). With respect to the total 100 moles of the epoxy groups of the epoxy compound (a-1), the total amount of acid groups capable of reacting with the epoxy groups from the polyanhydride (a-3) is 5 to 25 moles.

[0021] [9] The resin composition according to any one of [1] to [8] above, wherein the vinyl ester resin (B1) is a vinyl ester resin (B1-1) which is a reaction product of a resin precursor (Q2) and an unsaturated polycarboxylic acid (b1-4), and the resin precursor (Q2) is a reaction product of a resin precursor (Q1) and an unsaturated monocarboxylic acid (b1-3), and the resin precursor (Q1) is a reaction product of an epoxy compound (b1-1) having two epoxy groups in one molecule and a bisphenol compound (b1-2).

[0022]

[10] The resin composition according to any one of [1] to [9] above, wherein the unsaturated polyester resin (B2) is a reaction product of a diol (b2-1) and a polycarboxylic acid (b2-2), and the polycarboxylic acid (b2-2) includes: a polycarboxylic acid containing an ethylenically unsaturated group (b2-2-1) and a polycarboxylic acid not containing an ethylenically unsaturated group (b2-2-2).

[0023]

[11] The resin composition according to any one of [1] to

[10] above, wherein the Mw / Mn of the vinyl ester resin (A) is 3.0 or more, and the acid value is 20 KOHmg / g or more.

[0024]

[12] The resin composition according to any one of [1] to

[11] above, wherein the acid value of the resin (B) containing an ethylenically unsaturated group is 20 KOHmg / g or more.

[0025]

[13] The resin composition according to any one of [1] to

[12] above, wherein the resin (B) containing an ethylenically unsaturated group is only the vinyl ester resin (B1).

[0026]

[14] The resin composition according to any one of [1] to

[12] above, wherein the resin (B) containing an ethylenically unsaturated group includes the vinyl ester resin (B1) and the unsaturated polyester resin (B2).

[0027]

[15] For the resin composition described in

[14] above, the mass ratio of the vinyl ester resin (B1) to the unsaturated polyester resin (B2) (the vinyl ester resin (B1) / the unsaturated polyester resin (B2)) is 40 / 60 to 80 / 20.

[0028]

[16] For the resin composition according to any one of [1] to

[15] above, the compound (D) is at least one selected from magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide.

[0029] Effects of the Invention

[0030] According to the present invention, a resin composition can be provided which thickens at an appropriate rate over time at room temperature and has adhesiveness after thickening. BRIEF DESCRIPTION OF THE DRAWINGS

[0031]

Figure 1

[0032] The following shows the definitions and meanings of the terms and expressions in this specification.

[0033] Preferred numerical ranges can be arbitrarily combined with the preferred lower limit value and the upper limit value respectively.

[0034] (Meth)acrylic acid is a general term for acrylic acid and methacrylic acid. Similarly, (meth)acrylate is a general term for acrylate and methacrylate, and (meth)acryloyl is a general term for acryloyl and methacryloyl.

[0035] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are standard polystyrene equivalent molecular weights determined by gel permeation chromatography (GPC). Specifically, they are determined by the method described in the examples below. The molecular weight distribution is the calculated value of Mw / Mn.

[0036] The acid value of the vinyl ester resin and the unsaturated polyester resin is the amount [mg] of potassium hydroxide (KOH) required to neutralize 1 g of the vinyl ester resin or the unsaturated polyester resin, determined by the method according to JIS K6901:2008. Specifically, it is determined by the method described in the examples below.

[0037] The hydroxyl value of the vinyl ester resin is determined by the method according to JIS K6901:2008, and is the amount [mg] of potassium hydroxide (KOH) required to neutralize the acetic acid generated by the acetylation of 1 g of the vinyl ester resin. Specifically, it is determined by the method described in the examples below.

[0038] The viscosity of the resin composition is a value measured with a B-type viscometer at a temperature of 25°C. Specifically, it is measured by the method described in the examples below.

[0039] [Resin composition]

[0040] The resin composition according to an embodiment of the present invention (hereinafter, also referred to as this embodiment) is a resin composition containing: vinyl ester resin (A), a resin (B) containing an ethylenically unsaturated group, a monomer (C) containing an ethylenically unsaturated group, at least one compound (D) selected from oxides of Group 2 elements and hydroxides of Group 2 elements, and at least one compound (E) selected from water and compounds containing a hydroxyl group. The weight-average molecular weight Mw of the vinyl ester resin (A) is 6,000 or more, and the ratio Mw / Mn of the weight-average molecular weight Mw to the number-average molecular weight Mn is 2.0 or more. The resin (B) containing an ethylenically unsaturated group is at least one selected from a vinyl ester resin (B1) having a carboxyl group and a weight-average molecular weight Mw of less than 6,000, and an unsaturated polyester resin (B2) having a carboxyl group and a weight-average molecular weight Mw of less than 6,000.

[0041] The resin composition, by simultaneously containing a vinyl ester resin (A) having a specified weight-average molecular weight and a resin (B) containing an ethylenically unsaturated group having a carboxyl group and a specified weight-average molecular weight, thickens at an appropriate rate over time at room temperature and has adhesiveness after thickening. The reason is not yet clear, but it can be considered as follows.

[0042] For a resin composition containing a vinyl ester resin used for a lining member or the like, usually, hydroxyl groups from the vinyl ester resin, carboxylate anions from carboxyl groups, carbonyl groups, etc. coordinate to Group 2 element ions to form an apparently linear polymer, and the resin composition thickens. It is considered that the resin composition of this embodiment contains a higher molecular weight vinyl ester resin (A) with a weight-average molecular weight Mw of 6,000 or more, so that it thickens at an appropriate rate over time even at room temperature.

[0043] In addition, the resin composition of this embodiment contains a resin (B) containing an ethylenically unsaturated group, and the resin (B) containing an ethylenically unsaturated group contains at least one selected from a vinyl ester resin (B1) having a carboxyl group and a weight-average molecular weight Mw of less than 6,000, and an unsaturated polyester resin (B2) having a carboxyl group and a weight-average molecular weight Mw of less than 6,000. Such an unsaturated polyester resin (B2) easily forms a polymer having a network structure with a mesh-like shape that is not apparently linear. It is considered that as a result of forming a polymer having a network structure with a mesh-like shape, the resin composition exhibits adhesiveness.

[0044] <Vinyl ester resin (A)>

[0045] The vinyl ester resin (A) of the present embodiment is a resin having polymerizability based on an ethylenically unsaturated group, with a weight average molecular weight Mw of 6,000 or more, and the ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn is 2.0 or more.

[0046] The vinyl ester resin (A) can be used alone as one kind, or two or more kinds can be used in combination.

[0047] The content of the vinyl ester resin (A) in the resin composition, based on 100% by mass in total of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group, is preferably 30.0% by mass or more, more preferably 40.0% by mass or more, still more preferably 50.0% by mass or more, from the viewpoint of efficiently thickening, and is preferably 80.0% by mass or less, more preferably 75.0% by mass or less, still more preferably 70.0% by mass or less, from the viewpoint of further improving the adhesiveness after thickening. That is, the content of the vinyl ester resin (A) in the resin composition, based on 100% by mass in total of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group, is preferably 30.0 to 80.0% by mass, more preferably 40.0 to 75.0% by mass, still more preferably 50.0 to 70.0% by mass.

[0048] The content of the vinyl ester resin (A) in the resin composition, from the viewpoint of efficiently thickening, is preferably 10.0% by mass or more, more preferably 15.0% by mass or more, still more preferably 20.0% by mass or more, and from the viewpoint of further improving the adhesiveness after thickening, is preferably 50.0% by mass or less, more preferably 45.0% by mass or less, still more preferably 40.0% by mass or less. That is, the content of the vinyl ester resin (A) in the resin composition is preferably 10.0 to 50.0% by mass, more preferably 15.0 to 45.0% by mass, still more preferably 20.0 to 40.0% by mass.

[0049] In one aspect of the present invention, from the viewpoint of efficiently obtaining the effects of the present invention, in the resin composition of the present embodiment, based on 100% by mass in total of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group, preferably contains 50 to 70% by mass of the vinyl ester resin (A) and 30 to 50% by mass of the resin (B) containing an ethylenically unsaturated group.

[0050] The weight-average molecular weight Mw of the vinyl ester resin (A), from the viewpoint of efficient thickening, is preferably 6,500 or more, more preferably 7,000 or more, and still more preferably 7,500 or more. From the viewpoint of the ease of handling of the resin composition, it is preferably 35,000 or less, more preferably 25,000 or less, and still more preferably 15,000 or less. That is, the weight-average molecular weight Mw of the vinyl ester resin (A), as an example, is preferably 6,500 to 35,000, more preferably 7,000 to 25,000, and still more preferably 7,500 to 15,000.

[0051] The number-average molecular weight Mn of the vinyl ester resin (A), from the viewpoint of efficient thickening, is preferably 1,000 or more, more preferably 1,200 or more, and still more preferably 1,400 or more. From the viewpoint of the ease of handling of the resin composition, it is preferably 6,500 or less, more preferably 4,500 or less, and still more preferably 3,000 or less. That is, the number-average molecular weight Mn of the vinyl ester resin (A), as an example, is preferably 1,000 to 6,500, more preferably 1,200 to 4,500, and still more preferably 1,400 to 3,000.

[0052] The Mw / Mn of the vinyl ester resin (A), from the viewpoint of easy control of the synthesis conditions, is preferably 2.5 or more, more preferably 3.0 or more, and still more preferably 4.0 or more. From the viewpoint of suppressing the deviation of the physical properties of the resin composition and controlling the thickening rate, it is preferably 18 or less, more preferably 12 or less, and still more preferably 10 or less.

[0053] The acid value of the vinyl ester resin (A), from the viewpoint of efficiently thickening the resin composition, is preferably 20 KOHmg / g or more, more preferably 23 KOHmg / g or more, and still more preferably 25 KOHmg / g or more. Further, from the viewpoint of suppressing excessive thickening, it is preferably 80 KOHmg / g or less, more preferably 60 KOHmg / g or less, and still more preferably 50 KOHmg / g or less.

[0054] The hydroxyl value of the vinyl ester resin (A), from the viewpoint of efficiently thickening the resin composition, is preferably 30 KOHmg / g or more, more preferably 40 KOHmg / g or more, and still more preferably 50 KOHmg / g or more. Further, from the viewpoint of suppressing excessive thickening, it is preferably 80 KOHmg / g or less, more preferably 75 KOHmg / g or less, and still more preferably 70 KOHmg / g or less.

[0055] In one aspect of the present invention, it is preferred that the Mw / Mn of the vinyl ester resin (A) is 3.0 or more and the acid value is 20 KOHmg / g or more.

[0056] The vinyl ester resin (A) is not particularly limited as long as it is a vinyl ester resin having a weight-average molecular weight Mw of 6,000 or more and a ratio Mw / Mn of the weight-average molecular weight Mw to the number-average molecular weight Mn of 2.0 or more. However, from the viewpoint of thickening at an appropriate rate over time at room temperature, a vinyl ester resin (A1) which is an addition reaction product of a resin precursor (P1) and a polyanhydride (a-4) is preferred. The resin precursor (P1) is a reaction product of an epoxy compound (a-1) having two epoxy groups in one molecule, an unsaturated monocarboxylic acid (a-2), and a polyanhydride (a-3). With respect to a total of 100 moles of epoxy groups of the epoxy compound (a-1), the total amount of acid groups capable of reacting with epoxy groups from the polyanhydride (a-3) is 5 to 25 moles.

[0057] The vinyl ester resin (A1) is composed of multiple compounds. Depending on the mixing ratios of these multiple compounds, reaction conditions, etc., various complex reactions can occur involving multiple functional groups, which is common technical knowledge for those skilled in the art. Therefore, it is impossible or impractical in the current technology to directly determine and generally represent the specific chemical structure or properties of the vinyl ester resin (A1). Therefore, in the present invention, the vinyl ester resin (A1) is determined by the composition of the raw materials.

[0058] The vinyl ester resin (A1) is polymerized by crosslinking. Through the reaction of the epoxy groups of the epoxy compound (a-1) with the carboxyl groups of the unsaturated monocarboxylic acid (a-2), the epoxy groups of the epoxy compound (a-1) are ring-opened to generate hydroxyl groups, and the polyanhydride (a-3) undergoes ring-opening addition to these hydroxyl groups. Then, the carboxyl groups generated by the ring-opening addition of the polyanhydride (a-3) further react with the unreacted epoxy groups of the epoxy compound (a-1).

[0059] In addition, since the polyanhydrides (a-3) and (a-4) are added to the hydroxyl groups generated by the ring-opening of the epoxy groups of the epoxy compound (a-1), the total amount of hydroxyl groups is reduced, and a sharp increase in viscosity immediately after the preparation of the resin composition can be suppressed. As a result, the impregnation property with respect to the fibrous substrate constituting the lining member also becomes good.

[0060] In addition, through the addition of the polyanhydrides (a-3) and (a-4), carboxyl groups are also introduced, so the interaction with the compound (D) is enhanced, and the thickening rate of the resin composition is increased.

[0061] When producing the vinyl ester resin (A1), first, a resin precursor (P1) which is a reaction product of an epoxy compound (a-1) having two epoxy groups in one molecule, an unsaturated monocarboxylic acid (a-2), and a polyanhydride (a-3) is obtained.

[0062] The resin precursor (P1) can be obtained, for example, by mixing at least any one of a solvent and a reactive diluent, as needed, in an epoxide (a-1), an unsaturated monocarboxylic acid (a-2), and a polyanhydride (a-3) in a heat-stirrable reaction vessel, and heating with mixing for 1 to 8 hours in the presence of an esterification catalyst, preferably at 70 to 150 °C, more preferably at 80 to 140 °C, and further preferably at 90 to 130 °C.

[0063] The amount of the unsaturated monocarboxylic acid (a-2) used in synthesizing the resin precursor (P1) is preferably such that, relative to 100 moles of the total amount of epoxy groups of the epoxide (a-1), the total amount of acid groups of the unsaturated monocarboxylic acid (a-2) is 65 to 95 moles, more preferably 70 to 90 moles, and further preferably 75 to 85 moles.

[0064] If the total amount of acid groups of the unsaturated monocarboxylic acid (a-2) is 65 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxide (a-1), a sufficient amount of ethylenically unsaturated groups are introduced into the vinyl ester resin (A1), so that the resin composition is likely to exhibit good curability. In addition, if the total amount of acid groups of the unsaturated monocarboxylic acid (a-2) is 95 moles or less, the reaction product of the epoxide (a-1) and the unsaturated monocarboxylic acid (a-2) is sufficiently crosslinked with the polyanhydride (a-3), and a resin composition having good thickening properties is easily obtained.

[0065] Regarding the amount of the polyanhydride (a-3) used in synthesizing the resin precursor (P1), relative to 100 moles of the total amount of epoxy groups of the epoxide (a-1), the total amount of acid groups capable of reacting with epoxy groups from the polyanhydride (a-3) is 5 to 25 moles, preferably 7 to 23 moles, and more preferably 9 to 22 moles.

[0066] By having the total amount of acid groups capable of reacting with epoxy groups from the polyanhydride (a-3) be 5 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxide (a-1), the molecular weight can be increased by crosslinking the epoxide (a-1) and the polyanhydride (a-3), and the resin composition can be thickened efficiently. In addition, by having the total amount of acid groups capable of reacting with epoxy groups from the polyanhydride (a-3) be 25 moles or less, the degree of crosslinking of the epoxide (a-1) is easily controlled, gelation during synthesis is suppressed, and furthermore, the thickening rate of the resin composition is easily controlled.

[0067] The total amount of acid groups from the unsaturated monobasic acid (a-2) and the polybasic anhydride (a-3) used in synthesizing the synthetic resin precursor (P1) (the "acid groups" referred to herein mean the acid groups generated by hydrolysis of the polybasic anhydride (a-3). For example, when the polybasic anhydride (a-3) is a dibasic anhydride, the number of acid groups generated from 1 molecule is 2.) is preferably an amount such that it becomes 90 to 125 moles, more preferably 93 to 120 moles, and still more preferably 95 to 110 moles, relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1).

[0068] When the total amount of acid groups from the unsaturated monobasic acid (a-2) and the polybasic anhydride (a-3) is 90 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1), the amount of unreacted epoxy groups of the epoxy compound (a-1) is reduced, and it is easy to control the thickening rate of the resin composition. In addition, when the total amount of acid groups from the unsaturated monobasic acid (a-2) and the polybasic anhydride (a-3) is 125 moles or less, gelation during synthesis is suppressed, and in addition, the remaining of unreacted unsaturated monobasic acid (a-2) and polybasic anhydride (a-3) is suppressed, and it is easy to control the thickening rate of the resin composition.

[0069] After obtaining the resin precursor (P1), by reacting the resin precursor (P1) with the polybasic anhydride (a-4), the vinyl ester resin (A1) can be obtained.

[0070] By reacting the resin precursor (P1) with the polybasic anhydride (a-4), the epoxy compound (a-1) can be crosslinked through the same reaction mechanism as that of the polybasic anhydride (a-3), and carboxyl groups can be introduced into the resin precursor (P1). That is, when the polybasic anhydride (a-4) is added to the hydroxyl group generated by the ring-opening of the epoxy group of the epoxy compound (a-1), carboxyl groups are simultaneously generated. The carboxyl groups react with the unreacted epoxy groups of the epoxy compound (a-1) to carry out crosslinking. After all the epoxy groups have reacted, the carboxyl groups from the polybasic anhydride (a-4) directly remain, and the carboxyl groups are introduced into the resin.

[0071] The reaction of the resin precursor (P1) with the polybasic anhydride (a-4) is, for example, adding the polybasic anhydride (a-4) into the reaction vessel in which the resin precursor (P1) has been synthesized, and reacting at 70 to 150 °C, preferably 80 to 140 °C, and still more preferably 90 to 130 °C for 30 minutes to 4 hours in the presence of an esterification catalyst.

[0072] In the vinyl ester resin (A1), the amount of the polybasic anhydride (a-4) is preferably an amount such that the total amount of acid groups from the polybasic anhydride (a-4) becomes 3 to 40 moles, more preferably 3 to 35 moles, still more preferably 5 to 30 moles, and even more preferably 7 to 20 moles, relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1).

[0073] If the total amount of acid groups from the polyanhydride (a-4) is 3 moles or more per 100 moles of the total amount of epoxy groups of the epoxy compound (a-1), carboxyl groups in an amount required for increasing the thickening rate of the resin composition are introduced into the vinyl ester resin (A1). In addition, the hydroxyl groups generated by the ring-opening of the epoxy groups from the epoxy compound (a-1) are consumed by the addition of the polyanhydride (a-4), and an increase in viscosity after 1 hour from the preparation of the resin composition can be suppressed. Further, since the total amount of acid groups from the polyanhydride (a-4) is 60 moles or less, the thickening rate of the resin composition is easily controllable.

[0074] Examples of the esterification catalyst used for the production of the vinyl ester resin (A1) which is an addition reaction product of the resin precursor (P1) and the above polyanhydride (a-4) include tertiary amines such as triethylamine, triethylenediamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, 2,4,6-tris(dimethylaminomethyl)phenol, and diazabicyclooctane; phosphorus compounds such as triphenylphosphine and benzyltriphenylphosphonium chloride; diethylamine hydrochloride; quaternary ammonium salts such as trimethylbenzylammonium chloride and tetradecyldimethylbenzylammonium chloride; and lithium salts such as lithium chloride, lithium bromide, and lithium nitrate. These may be used alone or in combination of two or more. Among them, from the viewpoints of slowly promoting the synthesis reaction rate of the vinyl ester resin, suppressing gelation, and easily controlling the molecular weight distribution appropriately, at least one selected from phosphorus compounds and quaternary ammonium salts is preferred, and at least one selected from quaternary ammonium salts is more preferred.

[0075] The esterification catalyst used when producing the resin precursor (P1) may be the same as or different from the esterification catalyst used when producing the vinyl ester resin (A1) from the resin precursor (P1).

[0076] From the viewpoints of promoting the reaction and suppressing the thickening of the resin precursor (P1) simultaneously, the amount of the esterification catalyst used is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, and still more preferably 0.1 to 3 parts by mass with respect to 100 parts by mass in total of the epoxy compound (a-1), the unsaturated monocarboxylic acid (a-2), and the polyanhydride (a-3).

[0077] The solvent and the reactive diluent used for the production of the vinyl ester resin (A1) are not particularly limited as long as they are solvents inactive to the epoxy compound (a-1), the unsaturated monocarboxylic acid (a-2), the polyanhydride (a-3), and the polyanhydride (a-4). Examples thereof include known solvents having a boiling point of 70 to 270°C at 1 atmospheric pressure such as methyl isobutyl ketone, benzyl methacrylate, ethylene glycol dimethacrylate, phenoxyethyl methacrylate, and styrene. The solvent may be used alone or in combination of two or more.

[0078] As a reactive diluent, a monomer (C) having an ethylenically unsaturated group which is preferably inactive with respect to the epoxy compound (a-1), the unsaturated monocarboxylic acid (a-2), the polycarboxylic anhydride (a-3), and the polycarboxylic anhydride (a-4) is used.

[0079] (Epoxy compound (a-1))

[0080] The epoxy compound (a-1) is a compound having two epoxy groups in one molecule, and monomers, oligomers, and polymers can all be used, and there are no particular limitations on its molecular weight and molecular structure. The epoxy compound (a-1) may be a single type or two or more types may be used in combination.

[0081] Examples of the epoxy compound (a-1) include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and bisphenol AF type epoxy resins such as bisphenol type epoxy resins; phenol novolac type epoxy resins; tert-butylcatechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidyl ester type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, epoxy resins containing a spiro ring, cyclohexanedimethanol type epoxy resins, naphthylene ether type epoxy resins, etc. Among them, from the viewpoint of suppressing the viscosity of the resin composition from becoming too high and controlling the thickening rate, one or more selected from bisphenol type epoxy resins and phenol novolac type epoxy resins are preferred, and one or more selected from bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, and phenol novolac type epoxy resins are more preferred, and bisphenol A type epoxy resin is further preferred.

[0082] From the viewpoint of controlling the thickening rate, the epoxy equivalent of the epoxy compound (a-1) is preferably 170 to 1,000, more preferably 170 to 500, further preferably 170 to 400, and still more preferably 170 to 300.

[0083] From the viewpoint of ease of synthesis, the epoxy compound (a-1) is preferably liquid at 25°C, and in addition, an epoxy compound having an epoxy equivalent of 300 or less is preferably used.

[0084] (Unsaturated monocarboxylic acid (a-2))

[0085] The unsaturated monocarboxylic acid (a-2) is preferably a monocarboxylic acid having an ethylenically unsaturated group, and may be a single type or two or more types may be used in combination.

[0086] Examples of the unsaturated monobasic acid (a-2) include (meth)acrylic acid, crotonic acid, cinnamic acid, etc. Among them, from the viewpoint of obtaining a resin composition having versatility, reactivity during synthesis of the vinyl ester resin (A1), and good curability, at least one selected from (meth)acrylic acid and crotonic acid is preferred, (meth)acrylic acid is more preferred, and methacrylic acid is further preferred from the viewpoint of chemical resistance.

[0087] (Polyacid anhydride (a-3))

[0088] The polyanhydride (a-3) is an anhydride formed by dehydration condensation of at least two carboxyl groups of a compound having multiple carboxyl groups in one molecule. Among them, from the viewpoint of the ease of synthesis, molecular weight, ease of control of acid value and thickening rate of resin composition, dibasic acid anhydride is preferred. The polyanhydride (a-3) can be a single kind or two or more kinds can be used in combination.

[0089] As polyacid anhydride (a-3), for example, maleic anhydride, phthalic anhydride, succinic anhydride, endomethylenetetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, 3-methyl-1,2,3,6-tetrahydrophthalic anhydride, 4-methyl-1,2,3,6-tetrahydrophthalic anhydride, 3-methyl-hexahydrophthalic anhydride, 4-methyl-hexahydrophthalic anhydride, methyl-3,6-endomethylene-1,2,3,6-tetrahydrophthalic anhydride, trimellitic anhydride, etc. Among them, from the viewpoint of easy availability, reactivity, easy handling during synthesis, etc., maleic anhydride and phthalic anhydride are preferred, and maleic anhydride is more preferred.

[0090] (Polyacid anhydride (a-4))

[0091] The polyanhydride (a-4) is an anhydride formed by dehydration condensation of at least two carboxyl groups of a compound having multiple carboxyl groups in one molecule. Among them, from the viewpoints of ease of operation during synthesis of the vinyl ester resin (A1), ease of control of the molecular weight and acid value, and good viscosity characteristics of the resin composition, dibasic anhydrides are preferred. The polyanhydride (a-4) may be one alone or two or more may be used in combination.

[0092] Specific examples of the polybasic acid anhydride (a-4) include the same as those for the polybasic acid anhydride (a-3), and maleic anhydride is more preferred. The polybasic acid anhydride (a-3) and the polybasic acid anhydride (a-4) may be the same or different.

[0093] <Ethylenically unsaturated group-containing resin (B)>

[0094] The resin (B) containing an ethylenically unsaturated group in the present embodiment includes at least one selected from a vinyl ester resin (B1) having a carboxyl group and a weight average molecular weight Mw of less than 6,000 and an unsaturated polyester resin (B2) having a carboxyl group and a weight average molecular weight Mw of less than 6,000.

[0095] The resin (B) containing an ethylenically unsaturated group may contain a vinyl ester resin (B1) and not contain an unsaturated polyester resin (B2); it may not contain a vinyl ester resin (B1) and contain an unsaturated polyester resin (B2); or it may contain both a vinyl ester resin (B1) and an unsaturated polyester resin (B2).

[0096] The acid value of the resin (B) containing an ethylenically unsaturated group is preferably 20 KOHmg / g or more, more preferably 23 KOHmg / g or more, and further preferably 25 KOHmg / g or more, from the viewpoint of further improving the adhesiveness after thickening. In addition, from the viewpoint of efficiently thickening the resin composition, it is preferably 80 KOHmg / g or less, more preferably 60 KOHmg / g or less, and further preferably 50 KOHmg / g or less.

[0097] The content of the resin (B) containing an ethylenically unsaturated group in the resin composition, based on 100% by mass in total of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group, is preferably 20.0% by mass or more, more preferably 25.0% by mass or more, and further preferably 30.0% by mass or more, from the viewpoint of further improving the adhesiveness after thickening. From the viewpoint of ensuring the thickening property of the resin composition, it is preferably 70.0% by mass or less, more preferably 60.0% by mass or less, and further preferably 50.0% by mass or less. That is, the content of the vinyl ester resin (A) in the resin composition, based on 100% by mass in total of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group, is preferably 20.0 to 70.0% by mass, more preferably 25.0 to 60.0% by mass, and further preferably 30.0 to 50.0% by mass.

[0098] The content of the resin (B) containing an ethylenically unsaturated group in the resin composition, from the viewpoint of further improving the adhesiveness after thickening, is preferably 5.0% by mass or more, more preferably 6.0% by mass or more, and further preferably 7.0% by mass or more. From the viewpoint of ensuring the thickening property of the resin composition, it is preferably 40.0% by mass or less, more preferably 35.0% by mass or less, and further preferably 30.0% by mass or less. That is, the content of the resin (B) containing an ethylenically unsaturated group in the resin composition is preferably 5.0 to 40.0% by mass, more preferably 6.0 to 35.0% by mass, and further preferably 7.0 to 20.0% by mass.

[0099] The resin (B) containing an ethylenically unsaturated group may contain only a vinyl ester resin (B1), only an unsaturated polyester resin (B2), or may contain both a vinyl ester resin (B1) and an unsaturated polyester resin (B2).

[0100] The resin (B) containing an ethylenically unsaturated group may be used alone as one type, or two or more types may be used in combination.

[0101] The total content of the vinyl ester resin (B1) and the unsaturated polyester resin (B2) in the resin (B) containing an ethylenically unsaturated group is preferably 80% by mass or more, more preferably 90% by mass or more, still more preferably 95% by mass or more, and may be 100% by mass.

[0102] In one aspect of the present invention, the resin (B) containing an ethylenically unsaturated group preferably contains a vinyl ester resin (B1), more preferably only a vinyl ester resin (B1), from the viewpoints of efficiently thickening the resin composition and the strength physical properties and chemical resistance of the cured product.

[0103] In other aspects of the present invention, the resin (B) containing an ethylenically unsaturated group preferably contains a vinyl ester resin (B1) and an unsaturated polyester resin (B2) from the viewpoint of further improving the adhesiveness.

[0104] In addition, when the resin (B) containing an ethylenically unsaturated group contains a vinyl ester resin (B1) and an unsaturated polyester resin (B2), the mass ratio of the vinyl ester resin (B1) to the unsaturated polyester resin (B2) (vinyl ester resin (B1) / unsaturated polyester resin (B2)) is preferably 40 / 60 to 80 / 20, more preferably 50 / 50 to 70 / 30, still more preferably 55 / 45 to 65 / 35.

[0105] 〔Vinyl ester resin (B1)〕

[0106] The vinyl ester resin (B1) has a carboxyl group and a weight average molecular weight Mw of less than 6,000.

[0107] The vinyl ester resin (B1) may be used alone as one type, or two or more types may be used in combination.

[0108] The weight-average molecular weight Mw of the vinyl ester resin (B1) is preferably 2,000 or more, more preferably 3,000 or more, still more preferably 3,200 or more, from the viewpoint of achieving good thickening efficiency. From the viewpoint of further improving the adhesiveness after thickening, it is preferably 5,500 or less, more preferably 5,000 or less, still more preferably 4,800 or less. That is, the weight-average molecular weight Mw of the vinyl ester resin (B1) is preferably from 2,000 to 5,500, more preferably from 3,000 to 5,000, still more preferably from 3,200 to 4,800.

[0109] The number-average molecular weight Mn of the vinyl ester resin (B1) is preferably 400 or more, more preferably 600 or more, still more preferably 800 or more, from the viewpoint of achieving good thickening efficiency. From the viewpoint of further improving the adhesiveness after thickening, it is preferably 3,000 or less, more preferably 2,500 or less, still more preferably 2,000 or less. That is, the number-average molecular weight Mn of the vinyl ester resin (B1) is preferably from 400 to 3,000, more preferably from 600 to 2,500, still more preferably from 800 to 2,000.

[0110] The Mw / Mn of the vinyl ester resin (B1) is preferably 1.0 or more, more preferably 1.1 or more, still more preferably 1.3 or more, from the viewpoint of ease of synthesis control. From the viewpoint of suppressing variations in the physical properties of the resin composition and controlling the thickening rate, it is preferably 3.0 or less, more preferably 2.7 or less, still more preferably 2.5 or less.

[0111] The vinyl ester resin (B1) is not particularly limited as long as it is a vinyl ester resin having a carboxyl group and a weight-average molecular weight Mw of less than 6,000. However, from the viewpoint of further improving the adhesiveness after thickening, the vinyl ester resin (B1-1) which is a reaction product of a resin precursor (Q2) and an unsaturated polybasic acid (b1-4) is preferred. The resin precursor (Q2) is a reaction product of a resin precursor (Q1) and an unsaturated monobasic acid (b1-3), and the resin precursor (Q1) is a reaction product of an epoxy compound (b1-1) having two epoxy groups in one molecule and a bisphenol compound (b1-2).

[0112] The vinyl ester resin (B1-1) is composed of multiple compounds. Depending on the mixing ratio of these multiple compounds, reaction conditions, etc., multiple functional groups participate and various complex reactions can occur, which is common technical knowledge for those skilled in the art. Therefore, it is impossible or impractical to directly determine and generally represent the specific chemical structure or properties of the vinyl ester resin (B1-1) in the current technology. Therefore, in the present invention, the vinyl ester resin (B1-1) is determined by the composition of the raw materials.

[0113] When producing the vinyl ester resin (B1-1), first, a resin precursor (Q1) is obtained as a reaction product of an epoxy compound (b1-1) having two epoxy groups in one molecule and a bisphenol compound (b1-2).

[0114] The resin precursor (Q1) can be obtained, for example, by mixing at least one of a solvent and a reactive diluent, as needed, with the epoxy compound (b1-1) and the bisphenol compound (b1-2) in a heatable and stirrable container, and heating with mixing for 1 to 3 hours in the presence of an esterification catalyst, preferably at 70 to 160°C, more preferably at 80 to 155°C, and further preferably at 90 to 150°C.

[0115] The amount of the bisphenol compound (b1-2) used in the synthesis of the vinyl ester resin (B1-1) is preferably such that, relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), the total amount of hydroxyl groups of the bisphenol compound (b1-2) is 10 to 70 moles, more preferably 15 to 60 moles, and further preferably 20 to 55 moles.

[0116] If the total amount of hydroxyl groups of the bisphenol compound (b1-2) is 10 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), the molecular weight distribution of the vinyl ester resin (B1) becomes wider, and it is easy to control the viscosity of the resin composition. In addition, if the total amount of the bisphenol compound (b1-2) is 70 moles or less relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), the thickening rate of the resin composition is easy to control.

[0117] After obtaining the resin precursor (Q1), the resin precursor (Q2) is obtained by reacting the resin precursor (Q1) with an unsaturated monocarboxylic acid (b1-3).

[0118] The reaction of the resin precursor (Q1) with the unsaturated monocarboxylic acid (b1-3) is carried out, for example, by adding the unsaturated monocarboxylic acid (b1-3) in the reaction vessel in which the resin precursor (Q1) has been synthesized, in the presence of an esterification catalyst, and heating with mixing at 70 to 150°C, preferably 80 to 140°C, and further preferably 90 to 130°C for 30 minutes to 4 hours.

[0119] The amount of the unsaturated monocarboxylic acid (b1-3) used in the synthesis of the vinyl ester resin (B1) is preferably such that, relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), the total amount of acid groups of the unsaturated monocarboxylic acid (b1-3) is 30 to 100 moles, more preferably 35 to 80 moles, and further preferably 38 to 70 moles.

[0120] If the total amount of acid groups of the unsaturated monobasic acid (b1-3) is 30 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), since a sufficient amount of ethylenically unsaturated groups are introduced into the vinyl ester resin (B1), the resin composition is likely to exhibit good curability. Further, from the viewpoints of controlling the thickening rate, suppressing the offset of the cured resin composition, and manufacturing stability, it is preferred that the total amount of acid groups of the unsaturated monobasic acid (b1-3) is 100 moles or less relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1).

[0121] After obtaining the resin precursor (Q2), the vinyl ester resin (B1) is obtained by reacting the resin precursor (Q2) with an unsaturated polybasic acid (b1-4). By this reaction, carboxyl groups are introduced into the vinyl ester resin (B1).

[0122] The reaction of the resin precursor (Q2) with the unsaturated polybasic acid (b1-4) is carried out, for example, by adding the unsaturated polybasic acid (b1-4) in the reaction vessel in which the resin precursor (Q2) has been synthesized, in the presence of an esterification catalyst, and heating with mixing at 70 to 150 °C, preferably 80 to 140 °C, more preferably 90 to 130 °C for 30 minutes to 4 hours.

[0123] The amount of the unsaturated polybasic acid (b1-4) used in the synthesis of the vinyl ester resin (B1-1) is preferably such that the total amount of acid groups from the unsaturated polybasic acid (a-4) becomes 10 to 40 moles, more preferably 13 to 30 moles, and further preferably 15 to 25 moles relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1).

[0124] If the total amount of acid groups from the unsaturated polybasic acid (b1-4) is 10 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), since a sufficient amount of carboxyl groups are introduced into the vinyl ester resin (B1), the adhesiveness after thickening of the resin composition is improved. Further, from the viewpoint of controlling the thickening rate, it is preferred that the total amount of acid groups from the unsaturated polybasic acid (b1-4) is 40 moles or less relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1).

[0125] Examples of the esterification catalyst used in the production of the vinyl ester resin (B1-1) include the same substances as those used in the production of the vinyl ester resin (A1). Further, the esterification catalyst used in the production of the resin precursor (Q1), the esterification catalyst used in the production of the resin precursor (Q2), and the esterification catalyst used in the production of the vinyl ester resin (B1-1) from the resin precursor (Q2) may be the same or different.

[0126] In addition, in the production of the vinyl ester resin (B1-1), solvents, reactive diluents, polymerization inhibitors, etc. can be used as needed. Examples of the solvents and reactive diluents used in the production of the vinyl ester resin (B1-1) include the same substances as those used in the production of the vinyl ester resin (A1), and the preferred modes are also the same.

[0127] The vinyl ester resin (B1) may contain a vinyl ester resin (B1-2) which is a reaction product of an epoxy compound (b1-1) having two or more epoxy groups in one molecule and an unsaturated monocarboxylic acid (b1-3). If the resin composition contains the above reaction product, the resin composition is further thickened by the interaction between the hydroxyl group generated by the ring-opening of the epoxy group of the epoxy compound (b1-1) and the compound (D).

[0128] From the viewpoint of better thickening efficiency, the weight-average molecular weight Mw of the vinyl ester resin (B1-2) is preferably 400 or more, more preferably 600 or more, still more preferably 800 or more, and from the viewpoint of controlling the thickening rate of the resin composition, it is preferably 2,000 or less, more preferably 1,500 or less, still more preferably 1,200 or less.

[0129] From the viewpoint of enabling the resin composition to thicken efficiently, the number-average molecular weight Mn of the vinyl ester resin (B1-2) is preferably 400 or more, more preferably 500 or more, still more preferably 600 or more, and from the viewpoint of controlling the thickening rate of the resin composition, it is preferably 1,500 or less, more preferably 1,200 or less, still more preferably 1,000 or less.

[0130] From the viewpoint of the ease of synthesis control, the Mw / Mn of the vinyl ester resin (B1-2) is preferably 1.05 or more, more preferably 1.1 or more, and from the viewpoint of suppressing the deviation of the physical properties of the resin composition and controlling the thickening rate, it is preferably 2.0 or less, more preferably 1.7 or less, still more preferably 1.5 or less.

[0131] In the reaction product of the epoxy compound (b1-1) and the unsaturated monocarboxylic acid (b1-3), the amount of the unsaturated monocarboxylic acid (b1-3) is preferably such that the total amount of the acid groups of the unsaturated monocarboxylic acid (b1-3) becomes 80 moles or more, more preferably 90 moles or more, still more preferably 99 moles or more, preferably 120 moles or less, more preferably 110 moles or less, still more preferably 105 moles or less, relative to 100 moles of the total amount of the epoxy groups of the epoxy compound (b1-1).

[0132] If the total amount of acid groups of the unsaturated monocarboxylic acid (b1-3) is 80 moles or more relative to 100 moles of the total amount of epoxy groups of the epoxy compound (b1-1), since a sufficient amount of ethylenically unsaturated groups are introduced into the resin, the resin composition is likely to exhibit good curability.

[0133] The content of the vinyl ester resin (B1-2) in the vinyl ester resin (B1) is preferably 50% by mass or less, more preferably 40% by mass or less, still more preferably 35% by mass or less, and may be 0% by mass.

[0134] (Epoxy compound (b1-1))

[0135] The epoxy compound (b1-1) is a compound having two epoxy groups in one molecule, and monomers, oligomers, and polymers can all be used, and there are no particular limitations on its molecular weight and molecular structure. The epoxy compound (b1-1) can be a single type or a combination of two or more types.

[0136] As specific examples of the epoxy compound (b1-1), the same substances as those of the epoxy compound (a-1) can be cited, and the preferred modes are also the same.

[0137] (Bisphenol compound (b1-2))

[0138] There are no particular limitations on the molecular weight and molecular structure of the bisphenol compound (b1-2). The bisphenol compound (b1-2) can be a single type or a combination of two or more types.

[0139] Examples of the bisphenol compound (b1-2) include bisphenol A, bisphenol AP, bisphenol AF, bisphenol B, bisphenol BP, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol PH, bisphenol TMC, bisphenol Z, etc. Among them, from the viewpoint of controlling the thickening rate, at least one selected from bisphenol A, bisphenol E, bisphenol F, and bisphenol S is preferred, more preferably bisphenol A, bisphenol E, and bisphenol F, and still more preferably bisphenol A from the viewpoints of corrosion resistance, versatility, and cost.

[0140] (Unsaturated monocarboxylic acid (b1-3))

[0141] The unsaturated monocarboxylic acid (b1-3) is preferably a monocarboxylic acid having an ethylenically unsaturated group, and can be a single type or a combination of two or more types.

[0142] Examples of the unsaturated monocarboxylic acid (b1-3) include the same substances as those of the unsaturated monocarboxylic acid (a-2), and the preferred modes are also the same.

[0143] (Polybasic acid anhydride (b1-4))

[0144] The polybasic anhydride (b1-4) is an anhydride formed by dehydration condensation of at least two carboxyl groups of a compound having multiple carboxyl groups in one molecule. Among them, from the viewpoints of ease of synthesis and good viscosity characteristics, etc., a dibasic anhydride is preferred. The polybasic anhydride (b1-4) can be a single type or two or more types can be used in combination.

[0145] As the polybasic anhydride (b1-4), the same substances as the polybasic anhydride (a-3) can be cited, and the preferred modes are also the same.

[0146] [Unsaturated polyester resin (B2)]

[0147] The unsaturated polyester resin (B2) has a carboxyl group.

[0148] The unsaturated polyester resin (B2) can be a substance obtained by subjecting a polybasic acid component containing an unsaturated dibasic acid and, if necessary, a saturated polybasic acid to an esterification reaction with a polyol.

[0149] The unsaturated polyester resin (B2) can be used alone as one type or two or more types can be used in combination.

[0150] The weight average molecular weight Mw of the unsaturated polyester resin (B2), from the viewpoint of efficiently thickening, is preferably 1,000 or more, more preferably 1,500 or more, further preferably 2,000 or more, and from the viewpoint of further improving the adhesiveness after thickening, is preferably 10,000 or less, more preferably 8,000 or less, further preferably 6,000 or less. That is, the weight average molecular weight Mw of the unsaturated polyester resin (B2) is preferably 1,000 to 10,000, more preferably 1,500 to 8,000, further preferably 2,000 to 6,000.

[0151] The number average molecular weight Mn of the unsaturated polyester resin (B2), from the viewpoint of efficiently thickening, is preferably 400 or more, more preferably 500 or more, further preferably 600 or more, and from the viewpoint of further improving the adhesiveness after thickening, is preferably 5,000 or less, more preferably 4,000 or less, further preferably 3,000 or less.

[0152] The Mw / Mn of the unsaturated polyester resin (B2), from the viewpoint of ease of control of synthesis, is preferably 1.0 or more, more preferably 1.5 or more, further preferably 2.0 or more, and from the viewpoints of suppressing deviation of physical properties of the resin composition and controlling the thickening rate, is preferably 10.0 or less, more preferably 8.0 or less, further preferably 6.0 or less.

[0153] From the viewpoint of further improving the adhesiveness after thickening, the unsaturated polyester resin (B2) is a reaction product of a diol (b2-1) and a polybasic acid (b2-2), and the polybasic acid (b2-2) preferably contains: a polybasic acid (b2-2-1) containing an ethylenically unsaturated group and a polybasic acid (b2-2-2) not containing an ethylenically unsaturated group.

[0154] The unsaturated polyester resin (B2) as a reaction product of a diol (b2-1) and a polybasic acid (b2-2) can be produced, for example, by reacting a diol (a2-1), a polybasic acid (a2-2-1) containing an ethylenically unsaturated group, and a polybasic acid (a2-2-2) not containing an ethylenically unsaturated group in a heat-stirrable reaction vessel at 150 to 250 °C, preferably 170 to 240 °C, more preferably 180 to 230 °C for 8 to 15 hours.

[0155] The amount of the polybasic acid (b2-2) in the unsaturated polyester resin (B2) is preferably such that, relative to 100 moles of the total amount of the diol (b2-1), the total amount of the polybasic acid (b2-2) is 80 to 130 moles, more preferably 90 to 120 moles, and still more preferably 95 to 115 moles.

[0156] From the viewpoint of introducing a sufficient amount of carboxyl groups into the vinyl ester resin (B2) and improving the adhesiveness after thickening of the resin composition, the content ratio (molar ratio) of the structural units derived from the diol (b2-1) to the structural units derived from the polybasic acid (b2-2) in the unsaturated polyester resin (B2) is preferably 40:60 to 60:40, more preferably 45:55 to 55:45.

[0157] (diol (b2-1))

[0158] The diol (b2-1) is a compound having two hydroxyl groups in one molecule. From the viewpoint of further improving the adhesiveness after thickening, for example, alkylene diols, diol ethers, etc. are preferably used. The diol can be a single type or a combination of two or more types.

[0159] Examples of the alkanediol include ethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,6-hexanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,2-octanediol, 1,2-nonanediol, 1,4-cyclohexanediol, 1,8-octanediol, 1,9-nonanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,2-bis(4-hydroxycyclohexyl)propane, and hydrides of bisphenol A, bisphenol F, and bisphenol S, etc.

[0160] Examples of the diol ether include diethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, etc.

[0161] Among them, from the viewpoints of availability, ease of handling of the resin composition, and manufacturing cost, etc., 2-methyl-1,3-propanediol, ethylene glycol, propylene glycol, neopentyl glycol, diethylene glycol, dipropylene glycol, and hydride of bisphenol A are preferred, 2-methyl-1,3-propanediol, ethylene glycol, propylene glycol, neopentyl glycol, diethylene glycol, and dipropylene glycol are more preferred, and ethylene glycol, propylene glycol, and dipropylene glycol are further preferred.

[0162] (Polybasic acid (b2-2))

[0163] The polybasic acid (b2-2) preferably includes a polybasic acid (b2-2-1) without an ethylenically unsaturated group and a polybasic acid (b2-2-2) with an ethylenically unsaturated group.

[0164] 《Polybasic acid (b2-2-1) without an ethylenically unsaturated group》

[0165] The polybasic acid (b2-2-1) without an ethylenically unsaturated group is a compound having 2 carboxyl groups (including acid anhydrides) in one molecule and not having an ethylenically unsaturated group. The polybasic acid (b2-2-1) without an ethylenically unsaturated group can be a single kind or two or more kinds can be used in combination.

[0166] Examples of the polybasic acid (b2-2-1) that does not contain an ethylenically unsaturated group include phthalic anhydride, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, tetrahydrophthalic acid, endomethylenetetrahydrophthalic acid, hexahydrophthalic acid (1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid), naphthalenedicarboxylic acid, trimellitic acid, pyromellitic acid, chlorendic acid (chlorendic anhydride), tetrabromophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, succinic anhydride, chlorendic anhydride, trimellitic anhydride, pyromellitic anhydride, 4-methylphthalic acid, 5-methylisophthalic acid, 5-methylterephthalic acid, etc. Among them, phthalic anhydride is preferred from the viewpoint of further improving the adhesiveness after thickening.

[0167] The content of the polybasic acid (b2-2-1) that does not contain an ethylenically unsaturated group is preferably 20 mol% or more, more preferably 30 mol% or more, further preferably 40 mol% or more, still more preferably 50 mol% or more, preferably 80 mol% or less, more preferably 75 mol% or less, further preferably 70 mol% or less, still more preferably 65 mol% or less, based on 100 mol% of the polybasic acid (b2-2). That is, the content of the polybasic acid (b2-2-1) that does not contain an ethylenically unsaturated group is preferably 20 to 80 mol%, more preferably 30 to 75 mol%, further preferably 40 to 70 mol%, still more preferably 50 to 65 mol%, based on 100 mol% of the polybasic acid (b2-2).

[0168] 《Polybasic Acid (b2-2-2) Containing an Ethylenically Unsaturated Group》

[0169] The polybasic acid (b2-2-2) containing an ethylenically unsaturated group is a compound having at least 2 carboxyl groups (including acid anhydrides) and at least 1 ethylenically unsaturated group in one molecule. The polybasic acid (b2-2-2) containing an ethylenically unsaturated group may be a single type or two or more types may be used in combination.

[0170] Examples of the polybasic acid (b2-2-2) containing an ethylenically unsaturated group include maleic anhydride, fumaric acid, itaconic acid, citraconic acid, chloromaleic acid, etc. Among them, maleic anhydride and fumaric acid are preferred from the viewpoints of availability, ease of handling of the resin composition, and manufacturing cost, and maleic anhydride is preferably used.

[0171] The content of the polybasic acid (b2-2-2) having an ethylenically unsaturated group in the polybasic acid (b2-2) is preferably 20 mol% or more, more preferably 25 mol% or more, still more preferably 30 mol% or more, preferably 80 mol% or less, more preferably 70 mol% or less, still more preferably 60 mol% or less, based on 100 mol% of the polybasic acid (b2-2), from the viewpoint of further improving the adhesiveness after thickening. That is, the content of the polybasic acid (b2-2-2) having an ethylenically unsaturated group in the polybasic acid (b2-2) is preferably 20 to 80 mol%, more preferably 25 to 70 mol%, still more preferably 30 to 60 mol%, based on 100 mol% of the polybasic acid (b2-2).

[0172] <Monomer (C) having an ethylenically unsaturated group>

[0173] The monomer (C) having an ethylenically unsaturated group of the present embodiment is a monomer having polymerizability based on an ethylenically unsaturated group. Examples of the ethylenically unsaturated group include a vinyl group (including an allyl group), a (meth)acryloyl group, and the like. The monomer (C) having an ethylenically unsaturated group may be a single kind or two or more kinds may be used in combination.

[0174] Examples of the monomer having a vinyl group include styrene derivatives such as styrene, p-chlorostyrene, vinyltoluene, α-methylstyrene, dichlorostyrene, divinylbenzene, tert-butylstyrene, vinylbenzyl butyl ether, vinylbenzyl hexyl ether, and divinylbenzyl ether; vinyl acetate, diallyl fumarate, diallyl phthalate, triallyl isocyanurate, and the like.

[0175] Examples of the monomer having a (meth)acryloyl group include (meth)acrylic acid, monofunctional (meth)acrylate, polyfunctional (meth)acrylate, acryloylmorpholine, 2-hydroxyethyl (meth)acrylamide, 2-hydroxyethyl-N-methyl (meth)acrylamide, 3-hydroxypropyl (meth)acrylamide, and the like.

[0176] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, stearyl (meth)acrylate, tridecyl (meth)acrylate, phenoxyethyl (meth)acrylate, dicyclopentenyl oxyethyl (meth)acrylate, ethylene glycol monomethyl ether (meth)acrylate, ethylene glycol monoethyl ether (meth)acrylate, ethylene glycol monobutyl ether (meth)acrylate, ethylene glycol monohexyl ether (meth)acrylate, ethylene glycol mono-2-ethylhexyl ether (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, diethylene glycol monohexyl ether (meth)acrylate, diethylene glycol mono-2-ethylhexyl ether (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyl oxyethyl (meth)acrylate, tricyclodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, caprolactone-modified 2-hydroxyethyl (meth)acrylate, allyl (meth)acrylate, etc.

[0177] Examples of polyfunctional (meth)acrylates include alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,2-propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; polyoxyalkylene glycol di(meth)acrylates such as diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate; and trimethylolpropane di(meth)acrylate, glycerol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, pentaerythritol diacrylate monostearate, 1,3-bis((meth)acryloyloxy)-2-hydroxypropane, ethoxylated bisphenol A di(meth)acrylate, tris(2-(meth)acryloyloxyethyl) isocyanurate, etc.

[0178] Among them, as the monomer (C) containing an ethylenically unsaturated group, from the viewpoints of availability, good physical properties of the cured product, and manufacturing cost, styrene, vinyltoluene, methyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, dicyclopenteny (meth)acrylate, dicyclopentenyl oxyethyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate are preferred. More preferably, styrene, vinyltoluene, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, dicyclopenteny (meth)acrylate, dicyclopentenyl oxyethyl (meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate are preferred. Further preferably, styrene, benzyl (meth)acrylate, ethylene glycol di(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate are preferred.

[0179] From the viewpoint of reducing the viscosity of the resin composition immediately after production, the content of the monomer (C) containing an ethylenically unsaturated group in the resin composition is preferably 20.0% by mass or more, more preferably 30.0% by mass or more, and further preferably 35.0% by mass or more. From the viewpoint of efficient thickening, it is preferably 80.0% by mass or less, more preferably 75.0% by mass or less, and further preferably 65.0% by mass or less. That is, the content of the monomer (C) containing an ethylenically unsaturated group in the resin composition is preferably 20.0 to 80.0% by mass, more preferably 30.0 to 75.0% by mass, and further preferably 35.0 to 65.0% by mass.

[0180] <Compound (D)>

[0181] The compound (D) of the present embodiment is at least one selected from oxides of Group 2 elements and hydroxides of Group 2 elements.

[0182] The compound (D) may be a single type or two or more types may be used in combination.

[0183] The compound (D) interacts with the carboxyl groups and hydroxyl groups of the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group, and has an effect of thickening the resin composition over time.

[0184] Examples of the oxide of the Group 2 element include magnesium oxide, calcium oxide, barium oxide, etc.

[0185] Examples of the hydroxide of Group 2 elements include magnesium hydroxide, calcium hydroxide, barium hydroxide, etc. Among them, from the viewpoints of thickening effect, versatility, and cost, magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide are preferred, and magnesium oxide is more preferred.

[0186] From the viewpoint of efficiently thickening, the content of the compound (D) in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and still more preferably 0.1% by mass or more. From the viewpoint of controlling the thickening rate to an appropriate level, it is preferably 6.0% by mass or less, more preferably 5.0% by mass or less, and still more preferably 4.0% by mass or less. That is, the content of the compound (D) in the resin composition is preferably 0.01 to 6.0% by mass, more preferably 0.05 to 5.0% by mass, and still more preferably 0.1 to 4.0% by mass.

[0187] <Compound (E)>

[0188] The compound (E) of the present embodiment is at least one selected from water and a compound containing a hydroxyl group. By including the compound (E) in the resin composition, it is easy to control the thickening rate.

[0189] Examples of the compound containing a hydroxyl group include alcohols having a boiling point of 50°C or higher such as benzyl alcohol, stearyl alcohol, and isostearyl alcohol. In addition, hydroxycarboxylic acids such as lactic acid, glycerin, polyols, and (meth)acrylate esters containing a hydroxyl group can also be mentioned. These can be used alone or in combination of two or more. Among them, from the viewpoints of availability and cost, water and alcohol are preferred, and water is more preferred.

[0190] From the viewpoint of controlling the thickening rate, the content of the compound (E) in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and still more preferably 0.1% by mass or more. From the viewpoints of the strength and toughness of the cured product of the resin composition, it is preferably 3.0% by mass or less, more preferably 2.0% by mass or less, and still more preferably 1.0% by mass or less. That is, the content of the compound (E) in the resin composition is preferably 0.01 to 3.0% by mass, more preferably 0.05 to 2.0% by mass, and still more preferably 0.1 to 1.0% by mass.

[0191] <Photoinitiator (F)>

[0192] The resin composition of the present embodiment may further contain a photoinitiator (F).

[0193] As the photoinitiator (F), a known photoinitiator such as an intramolecular cleavage type can be used, and one or more kinds can be appropriately selected according to the wavelength of the irradiation light from the light source used when curing the resin composition.

[0194] A resin composition containing a photoinitiator (F) becomes a cured product by irradiating a light source having a light emission wavelength equivalent to the absorption wavelength of the photoinitiator (F).

[0195] As the photoinitiator (F), there is no particular limitation as long as it is a substance that generates free radicals by light irradiation. Examples thereof include benzoin and its alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, and 4-(1-tert-butyldioxy-1-methylethyl)acetophenone; α-hydroxyalkylacetophenones such as 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-2-methyl-1-phenyl-propan-1-one; anthraquinones such as 2-methylanthraquinone, 2-pentylanthraquinone, 2-tert-butylanthraquinone, and 1-chloroanthraquinone; thioxanthones such as 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, and 2-chlorothioxanthone; ketals such as acetophenone dimethyl ketal and benzil dimethyl ketal; benzophenones such as benzophenone, 4-(1-tert-butyldioxy-1-methylethyl)benzophenone, and 3,3',4,4'-tetra(tert-butyldioxycarbonyl)benzophenone; morpholines such as 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one; acylphosphine oxides such as phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and xanthones and the like.

[0196] From the viewpoint of reactivity, the photoinitiator (F) is preferably an intramolecular cleavage type photoinitiator that does not require a hydrogen donor. In addition, since active species are generated by absorbing light with a wavelength of 315 to 460 nm, 2,2-dimethoxy-2-phenylacetophenone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 1-hydroxycyclohexyl phenyl ketone, which efficiently generate active species in the above wavelength range, are preferred.

[0197] From the viewpoint of curability, the content of the photopolymerization initiator (F) in the resin composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and still more preferably 0.1% by mass or more. From the viewpoints of suppressing heat generation, cracks, etc. during the curing of the resin composition, and from the viewpoint of the balance of physical properties such as the strength, toughness, heat resistance, and chemical resistance of the cured product of the resin composition, it is preferably 3.0% by mass or less, more preferably 2.0% by mass or less, and still more preferably 1.0% by mass or less. That is, the content of the photopolymerization initiator (F) in the resin composition is preferably 0.01 to 3.0% by mass, more preferably 0.05 to 2.0% by mass, and still more preferably 0.1 to 1.0% by mass.

[0198] <Other components>

[0199] The resin composition of the present embodiment may contain, as other components, for example, other resins, polymerization inhibitors, thixotropic agents, curing accelerators, catalysts, thickening aids, curing retarders, surfactants, surface conditioners, wetting dispersants, defoamers, leveling agents, coupling agents, light stabilizers, waxes, flame retardants, plasticizers, fillers, internal mold release agents, low shrinkage agents, toners, viscosity reducers, anti-separation agents, compatibilizers, pigments, and other additives. The content of the above additives is not particularly limited as long as it is within a range that does not hinder the effects of the present invention.

[0200] The thixotropic agent can be used to adjust the miscibility and fluidity of the resin composition. Examples of the thixotropic agent include organic thixotropic agents and inorganic thixotropic agents. They can be used alone or in combination of two or more.

[0201] When the resin composition of the present embodiment contains a thixotropic agent, its content is preferably 0.01 to 5% by mass, more preferably 0.1 to 3% by mass in the composition.

[0202] Examples of the organic thixotropic agent include hydrogenated castor oil-based, amide-based, polyethylene oxide-based, vegetable oil polymerized oil-based, surfactant-based, and composite systems using them in combination. Specifically, "Flowon (registered trademark) SP-1000AF" (manufactured by Kyoeisha Chemical Co., Ltd.), "Disparlon (registered trademark) 6900-20X" (Kusumoto Chemicals, Ltd.), etc. can be mentioned.

[0203] Examples of the inorganic thixotropic agents include silica and bentonite that have been subjected to hydrophobic treatment or hydrophilic treatment. Specific examples of the hydrophobic inorganic thixotropic agents include "Reolosil (registered trademark) PM-20L" (manufactured by Tokuyama Corporation), "Aerosil (registered trademark) R-106" (manufactured by Nippon Aerosil Co., Ltd.), "CAB-O-SIL (registered trademark)" (manufactured by Cabot Corporation), etc. Specific examples of the hydrophilic inorganic thixotropic agents include "Aerosil (registered trademark)-200" (manufactured by Nippon Aerosil Co., Ltd.). It should be noted that when using hydrophilic calcined silica, the combined use of the thixotropic modifiers "BYK (registered trademark)-R605" and "BYK (registered trademark)-R606" (both manufactured by BYK) is effective for moderately controlling the thickening rate.

[0204] <Viscosity of the resin composition>

[0205] From the viewpoint of impregnation property into the fiber substrate, the viscosity at 25°C after 1 hour from the preparation of the resin composition is preferably 0.1 to 4.0 Pa·s, more preferably 0.2 to 3.5 Pa·s, and further preferably 0.3 to 3.0 Pa·s.

[0206] From the viewpoint of thickening property, the viscosity at 25°C after 2 days from the preparation of the resin composition is preferably 30 to 1,500 Pa·s, more preferably 40 to 1,000 Pa·s, and further preferably 50 to 500 Pa·s.

[0207] From the viewpoint of thickening property, the viscosity at 25°C after 5 days from the preparation of the resin composition is preferably 400 to 3,500 Pa·s, more preferably 450 to 2,500 Pa·s, further preferably 500 to 2,200 Pa·s, and even more preferably 500 to 2,000 Pa·s.

[0208] [Manufacturing method of the resin composition]

[0209] The resin composition according to the present embodiment can be manufactured by mixing a vinyl ester resin (A), a resin (B) containing an ethylenically unsaturated group, a monomer (C) containing an ethylenically unsaturated group, a compound (D), and a compound (E). If necessary, other components can be added and mixed.

[0210] The order of mixing is not particularly limited. For example, the vinyl ester resin (A) and the resin (B) containing an ethylenically unsaturated group are mixed and dissolved in the monomer (C) containing an ethylenically unsaturated group, and the compound (D), the compound (E), and optional other components are added and mixed to obtain the resin composition.

[0211] The mixing method is not particularly limited, and for example, a disperser, a planetary mixer, a kneader, etc. can be used. The kneading temperature is preferably 10 to 40°C, more preferably 15 to 30°C, and further preferably 20 to 30°C from the viewpoint of ease of mixing, etc.

[0212] [Use of the resin composition]

[0213] Even when the resin composition of the present embodiment is used as a composite material with a fiber substrate, a cured product having good physical properties can be obtained, and it is suitable for use as a lining member.

[0214] [Composite material]

[0215] The composite material in the present embodiment includes a fiber substrate (G) impregnated with the above resin composition (hereinafter, also referred to as a resin-impregnated substrate), and is a material for a lining member.

[0216] As the composite material, a material in which the resin composition is impregnated into the fiber substrate (G) and thickened by storing (curing) for a certain period is preferable. If such a composite material is used, a lining member having excellent shape retention can be obtained.

[0217] As the type of fiber of the fiber substrate (G), from the viewpoint of mechanical strength, etc., examples include organic fibers such as amide, aramid, vinylon, polyester, and phenol, carbon fiber, glass fiber, metal fiber, ceramic fiber, etc., so-called reinforcing fibers, and their composite fibers. The fiber substrate (G) can be a single type or two or more types can be used in combination. Among them, aramid fiber, carbon fiber, and glass fiber are preferable, and glass fiber is more preferable from the viewpoints of strength, ease of obtaining, and price, and glass fiber having light transmissibility and polyester fiber are further preferable.

[0218] For example, in the case of glass fiber, the generally used filament diameter is preferably 1 to 15 μm, more preferably 3 to 10 μm.

[0219] As the form of the fiber substrate (G), examples include sheets, chopped strands, chops, ground fibers, etc. As the sheet, examples include a material formed by aligning a plurality of reinforcing fibers in one direction, two-way fabrics such as plain weave fabrics and twill weave fabrics, multi-axis fabrics, non-crimp fabrics, non-woven fabrics, felts, knitted fabrics, tapes, papers obtained by papermaking of reinforcing fibers, etc. The form of the fiber substrate (G) can be a single type or two or more types can be used in combination, and in addition, it can be a single layer or multiple layers can be laminated.

[0220] [Lining member]

[0221] The lining member refers to a material used for repairing pipes such as existing pipes. The repair of the pipe is carried out by arranging the lining member along the inner circumference of the inner surface of the pipe, pressing the lining member against the inner surface of the pipe, and then irradiating light such as ultraviolet light or visible light to cure the resin composition contained in the lining member. It should be noted that in this specification, arranging the lining member along the inner circumference of the inner surface of the above-mentioned pipe, pressing the lining member against the inner surface of the pipe, and then irradiating ultraviolet light or visible light or the like to cure the resin composition contained in the lining member is also referred to as the construction of pipe regeneration.

[0222] The lining member is in a cylindrical shape and includes a composite material in which a resin composition is impregnated in a fiber base material (G).

[0223] From the viewpoint of the ease of the construction of pipe regeneration, the lining member preferably has an inner film on the innermost layer of the inner surface, an outer film on the outermost layer of the outer surface, and a composite material layer containing the composite material between the inner film and the outer film, or has an outer film on the innermost layer of the inner surface, an inner film on the outermost layer of the outer surface, and a composite material layer containing the composite material between the inner film and the outer film. In addition, the lining member having an outer film on the innermost layer of the inner surface, an inner film on the outermost layer of the outer surface, and a composite material layer containing the composite material between the inner film and the outer film is preferably used for the inversion construction method of introducing the lining member into the inner surface of the pipe while inverting the lining member.

[0224] The lining member may have other layers as needed. In addition, each layer may be a single layer or multiple layers may be laminated.

[0225] The lining member is preferably in a cylindrical shape having substantially the same diameter according to the diameter of the inner surface of the pipe. Thereby, the strength of the repaired pipe is improved.

[0226] The inner diameter of the lining member is not particularly limited, but is preferably 100 to 1500 mm, more preferably 130 to 1200 mm, and further preferably 150 to 1000 mm.

[0227] If the inner diameter of the lining member is 100 mm or more, the construction of light curing is easy, and if the inner diameter of the lining member is 1500 mm or less, the workability during the construction of pipe regeneration is good.

[0228] <Inner film>

[0229] As the inner film, for example, resin films such as polyethylene film, polypropylene film, polyethylene terephthalate film, polyamide film, and cellophane film can be used. The inner film needs to be permeable to the light irradiated from the light irradiation device during the construction of pipe regeneration. Thereby, the lining member can be cured efficiently and the pipe regeneration can be carried out appropriately. It should be noted that the inner film can be peeled off after curing the lining member.

[0230] The thickness of the inner membrane is not particularly limited, but is preferably 50 to 200 μm, more preferably 80 to 170 μm. If the thickness of the inner membrane is 50 μm or more, there is no breakage or wrinkling of the inner membrane during or before the construction of pipe regeneration, and sufficient strength can be imparted to the pipe. If the thickness of the inner membrane is 200 μm or less, the manufacture of the lining member becomes easy, and in addition, the workability during the construction of pipe regeneration is good.

[0231] <Outer membrane>

[0232] As the outer membrane, a resin film can be used in the same manner as the inner membrane. The outer membrane preferably has light-shielding properties. Thereby, it is possible to suppress the curing of the lining member due to light from the outside before the construction of pipe regeneration.

[0233] In addition, during the construction of pipe regeneration, it is possible to suppress the light irradiated from passing through the lining member, and the lining member can be photocured efficiently. As the outer membrane having light-shielding properties, for example, a laminated film having a colored film layer such as yellow between two transparent polyethylene films can be used.

[0234] The thickness of the outer membrane is not particularly limited, but is preferably 5 to 100 μm, more preferably 10 to 90 μm. If the thickness of the outer membrane is 5 μm or more, there is no breakage or wrinkling of the outer membrane before the light irradiation during the construction of pipe regeneration, and sufficient strength can be imparted to the pipe. If the thickness of the outer membrane is 100 μm or less, the manufacture of the lining member becomes easy, and in addition, the workability during the construction of pipe regeneration is good.

[0235] [Manufacturing method of lining member]

[0236] As the manufacturing method of the lining member, a conventionally well-known manufacturing method can be used, but the first embodiment or the second embodiment described later is preferred.

[0237] The manufacturing method of the lining member in the first embodiment of the present invention includes the following steps 1 and 2.

[0238] The manufacturing method of the lining member in the second embodiment of the present invention includes the following steps 1 to 3.

[0239] <Step 1>

[0240] Step 1 is a step of impregnating a resin composition into a fiber base material (G) to obtain a composite material (resin composition-impregnated base material). In Step 1, the resin composition can be impregnated into the fiber base material (G) on which the inner membrane and the outer membrane are not laminated, or the fiber base material (G) having the inner membrane and the outer membrane laminated on the surface can be used.

[0241] Note that when using a fibrous substrate (G) with an inner film and an outer film laminated on its surface, the resin composition is impregnated into the fibrous substrate (G) through at least one of the inner film and the outer film.

[0242] The fibrous substrate (G) used in Step 1 can be cylindrical, sheet-shaped, or strip-shaped.

[0243] In the first embodiment, the fibrous substrate (G) is preferably cylindrical, and in the second embodiment, the fibrous substrate (G) is preferably sheet-shaped or strip-shaped.

[0244] From the perspective of reducing impregnation defects and enabling the resin composition to be uniformly impregnated, the time for impregnating the resin composition into the fibrous substrate (G) is preferably 0.5 to 24 hours, more preferably 1 to 10 hours, and further preferably 1.5 to 5 hours.

[0245] The time from after the resin composition is prepared, that is, after the resin composition is manufactured, to the completion of impregnation of the resin composition is preferably 1 to 30 hours, more preferably 2 to 24 hours, and further preferably 5 to 10 hours.

[0246] <Step 2>

[0247] Step 2 is the step of laminating the inner film and the outer film on the fibrous substrate (G).

[0248] Regarding the method of laminating the inner film and the outer film, there is no particular limitation, but examples include a method of laminating by applying a liquid film composition to the fibrous substrate (G) and curing it, a method of laminating the film on the fibrous substrate (G) or a composite material via an adhesive layer, a method of directly laminating the film on the fibrous substrate (G) or a composite material, etc. The inner film and the outer film can be laminated using different methods respectively, or the same method can be used for lamination.

[0249] The inner film and the outer film can each independently be laminated before or after impregnating the resin composition into the fibrous substrate (G). In addition, it can be carried out before or after Step 3 described below.

[0250] <Step 3>

[0251] Step 3 is the step of processing into a cylindrical shape. Note that when using a fibrous substrate (G) that is already cylindrical, Step 3 does not need to be carried out, and Step 3 is carried out when using a sheet-shaped or strip-shaped fibrous substrate (G).

[0252] In Step 3, by winding the lining member material around a mandrel having a diameter approximately the same as the inner diameter of the pipe and connecting them together with the resin composition contained in the resin-impregnated substrate, it is processed into a cylindrical shape.

[0253] Specifically, in the case where the composite material is in sheet form, after winding around the mandrel, the two sides in the longitudinal direction are overlapped by about 1 to 10 cm and joined together with the resin composition contained in the composite material. In addition, in the case where the composite material is in strip form, the composite material is wound spirally while overlapping by about 1 to 10 cm, and the overlapping portion is joined together with the resin composition contained in the composite material.

[0254] In Step 3, if the composite material is wound around the mandrel in a state where the inner membrane is pre - arranged on the mandrel, it is not necessary to laminate the inner membrane on the fiber substrate (G) or the composite material, and it is easy to remove the mandrel after winding the composite material, so this is preferred.

[0255] In addition, from the viewpoint of productivity, it is preferred to laminate the outer membrane after processing into a cylindrical shape.

[0256] In Step 3, the overlapping portion of the composite material is joined together with the resin composition. Therefore, the viscosity of the resin composition contained in the composite material at this time is preferably a viscosity having moderate adhesiveness, preferably 30 to 1,500 Pa·s, more preferably 40 to 1,000 Pa·s, and further preferably 50 to 500 Pa·s.

[0257] If the viscosity of the resin composition contained in the composite material is 30 Pa·s or more, the resin composition has moderate adhesiveness, the resin composition will not be offset in the composite material, and can maintain a state of being uniformly contained. In addition, if the viscosity of the resin composition is 1,500 Pa·s or less, it is easy to process into a cylindrical shape.

[0258] The manufacturing method of the lining member may further include a curing process in addition to the above - mentioned Steps 1 to 3.

[0259] The curing process is a process for appropriately thickening the resin composition until it reaches a viscosity suitable for each process. It is preferably set after impregnating the fiber substrate (G) with the resin composition and before the construction of pipe regeneration.

[0260] The curing temperature in the curing process is preferably 10 to 40 °C, more preferably 15 to 30 °C, and further preferably 20 to 30 °C. The curing temperature can be appropriately adjusted according to the target viscosity of the resin composition, the curing time, etc.

[0261] In the first embodiment, it is preferred to set a curing process between the completion of the above - mentioned Steps 1 and 2 and the construction of pipe regeneration. The curing time is preferably 6 hours to 3.5 days, more preferably 12 hours to 3 days, and further preferably 1 to 2 days.

[0262] In the second embodiment, it is preferable to provide a curing process immediately after step 1. In addition, it is preferable to provide a curing process between after step 3 and the construction of pipe regeneration. The curing time immediately after step 1 is preferably 12 hours to 3 days, more preferably 1 day to 2.5 days, and still more preferably 1.5 to 2 days. If the curing time is within the above range, the resin composition exhibits appropriate adhesiveness and can join the overlapping portions of the composite material together with sufficient strength.

[0263] The curing time between after step 3 and the construction of pipe regeneration is preferably 6 hours to 3.5 days, more preferably 12 hours to 3 days, and still more preferably 1 to 2 days.

[0264] From the viewpoint of quality stability, the storage period of the lining member in which the viscosity of the resin composition has reached 400 to 3,500 Pa·s after the curing process is preferably 1 to 6 months, more preferably 2 to 5 months.

[0265] Examples

[0266] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited by these examples.

[0267] [Each Material]

[0268] Details of the compounds used in the following synthesis examples are shown below.

[0269] ·Epoxy compound (1): Bisphenol A epoxy resin; "jER (registered trademark) 834", manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 245

[0270] ·Epoxy compound (2): Bisphenol A epoxy resin; "Epomic (registered trademark) R140P", manufactured by Mitsui Chemicals, Inc., epoxy equivalent 188

[0271] ·Tetradecyldimethylbenzylammonium chloride: "Nissan Cation (registered trademark) M2-100R", manufactured by NOF Corporation, purity exceeding 90% by mass

[0272] ·2,4,6-Tris(dimethylaminomethyl)phenol: "Seaquol TDMP", manufactured by Seiko Chemical Co., Ltd., purity exceeding 95% by mass

[0273] ·Triethylamine: manufactured by Daicel Corporation

[0274] ·Benzyl methacrylate: "Light Ester BZ", manufactured by Kyoeisha Chemical Co., Ltd.

[0275] ·Phenoxyethyl methacrylate: "Light Ester PO", manufactured by Kyoeisha Chemical Co., Ltd.

[0276] [Synthesis of Vinyl Ester Resin]

[0277] <Synthesis Example A1-a>

[0278] In a 5 L four-necked detachable flask equipped with a stirrer, a reflux condenser, a gas inlet tube, and a thermometer, 1260 g of an epoxy compound (1), 0.7 g of methylhydroquinone as a polymerization inhibitor (0.04 parts by mass based on 100 parts by mass in total of the epoxy compound (a-1), unsaturated monocarboxylic acid (a-2), and polyanhydride (a-3)), and 3.4 g of tetradecyldimethylbenzylammonium chloride as a catalyst (0.2 parts by mass based on 100 parts by mass in total of the epoxy compound (a-1), unsaturated monocarboxylic acid (a-2), and polyanhydride (a-3)) were added, and the mixture was heated to 110 °C. Then, 350 g of methacrylic acid as the unsaturated monocarboxylic acid (a-2) (the acid group of methacrylic acid was 80 moles relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1)) and 100 g of maleic anhydride as the polyanhydride (a-3) (maleic anhydride was 20 moles relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1), that is, the total amount of acid groups capable of reacting with epoxy groups from maleic anhydride was 20 moles relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1)) were added dropwise over about 30 minutes, and then the mixture was reacted for about 4 hours to synthesize a resin precursor (P1). Subsequently, 50 g of maleic anhydride as the polyanhydride (a-4) (maleic anhydride was 10 moles relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1), that is, the total amount of acid groups capable of reacting with epoxy groups from maleic anhydride was 10 moles relative to 100 moles of the total amount of epoxy groups of the epoxy compound (a-1)) was added, and the mixture was reacted for about 2 hours to obtain a vinyl ester resin (A1-a) as the vinyl ester resin (A1).

[0279] The reaction product containing the vinyl ester resin (A1-a) was cooled to 90 °C, and 950 g of benzyl methacrylate as a reactive diluent and a monomer (C) containing an ethylenically unsaturated group (35% by mass based on the total amount of the blended components) was added to obtain a mixture of the vinyl ester resin (A1-a) and benzyl methacrylate (mass ratio 65 / 35).

[0280] The blending amounts of each component are shown in Table 1.

[0281] [Resin Containing an Ethylenically Unsaturated Group]

[0282] <Synthesis Example B1-1-a>

[0283] In a 5 L four-necked detachable flask equipped with a stirrer, a reflux condenser, a gas inlet tube, and a thermometer, 1260 g of an epoxide (2) and 358 g of bisphenol A as bisphenol (b1-2) (the total amount of hydroxyl groups of bisphenol A was 47 moles with respect to 100 moles of the total amount of epoxy groups of the epoxide (b1-1)) were added, and the mixture was heated to 80°C. Then, 3.2 g of tetradecyldimethylbenzylammonium chloride as a catalyst (0.2 parts by mass with respect to 100 parts by mass of the total of the epoxide (b1-1) and bisphenol (b1-2)) was added, and the mixture was heated to 145°C and reacted for 1 hour to synthesize a resin precursor (Q-1). Then, after cooling to 110°C, 1337 g of benzyl methacrylate as a reactive diluent (40% by mass based on the total amount of the mixed components), 0.03 g of 5% copper naphthenate as a polymerization inhibitor (0.002 parts by mass with respect to 100 parts by mass of the total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), 0.56 g of methylhydroquinone (0.03 parts by mass with respect to 100 parts by mass of the total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), 1.05 g of trimethylhydroquinone (0.056 parts by mass with respect to 100 parts by mass of the total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), and 5.0 g of tetradecyldimethylbenzylammonium chloride as an esterification catalyst (0.27 parts by mass with respect to 100 parts by mass of the total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)) were added. After heating to 110°C, 247 g of methacrylic acid as an unsaturated monocarboxylic acid (b1-3) (the total amount of acid groups of methacrylic acid was 43 moles with respect to 100 moles of the total amount of epoxy groups of the epoxide (b1-1)) was added dropwise over about 30 minutes, and the mixture was reacted for about 2 hours to synthesize a resin precursor (Q-2). Then, 131 g of maleic anhydride as an unsaturated polycarboxylic acid (b1-4) (maleic anhydride was 20 moles with respect to 100 moles of the total amount of epoxy groups of the epoxide (b-1), that is, the acid groups capable of reacting with epoxy groups from maleic anhydride were 20 moles with respect to 100 moles of the total amount of epoxy groups of the epoxide (b1-1)) was added, and the mixture was reacted for about 1 hour to obtain a vinyl ester resin (B1-1-a) as a vinyl ester resin (B1-1) having a carboxyl group and an Mw of 4239.

[0284] The reaction product was cooled to 90°C to obtain a mixture containing 60% by mass of the vinyl ester resin and 40% by mass of benzyl methacrylate based on the total mass of the mixed components.

[0285] The blending amounts of the respective components are shown in Table 2.

[0286] <Synthesis Example B1-1-b and B1-1-c>

[0287] Except for the compounding composition shown in Table 1, the synthesis was carried out in the same manner as in Synthesis Example B1-1-a to obtain vinyl ester resins (B1-1-b) and (B1-1-c) as the vinyl ester resin (B1-1).

[0288] The reaction product was cooled to 90 °C to obtain a mixture containing 65% by mass of vinyl ester resin and 35% by mass of benzyl methacrylate based on the total mass of the compounding components.

[0289] The compounding amounts of the respective components are shown in Table 2.

[0290] <Comparative Synthesis Example B1'-a>

[0291] In a 5 L four-necked detachable flask equipped with a stirrer, a reflux condenser, a gas inlet tube, and a thermometer, 1512 g of an epoxy compound (2) and 429 g of bisphenol A (manufactured by Mitsubishi Chemical Corporation) (the total amount of hydroxyl groups of bisphenol A was 47 moles relative to the total amount of epoxy groups of the epoxy compound (b1-1)) were added and heated to 80 °C. Then, 3.9 g of triethylamine as a catalyst (0.2 parts by mass relative to 100 parts by mass in total of the epoxy compound (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)) was added, and the mixture was heated to 145 °C and reacted for 1 hour to synthesize a resin precursor (Q-3). Then, after cooling to 110 °C, 429 g of styrene as a reactive diluent (10% by mass based on the total mass of the compounding components), 0.04 g of 5% copper naphthenate as a polymerization inhibitor (0.0019 parts by mass relative to 100 parts by mass in total of the epoxy compound (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), 1.3 g of trimethylhydroquinone (0.056 parts by mass relative to 100 parts by mass in total of the epoxy compound (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), and 6.9 g of 2,4,6-tris(dimethylaminomethyl)phenol as an esterification catalyst (0.3 parts by mass relative to 100 parts by mass in total of the epoxy compound (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)) were added, and the mixture was heated to 110 °C. Further, 365 g of methacrylic acid as the unsaturated monocarboxylic acid (b1-3) (the total amount of acid groups of methacrylic acid was 53 moles relative to the total amount of epoxy groups of the epoxy compound (b1-1)) was added dropwise over about 30 minutes, and then the mixture was heated to 130 °C and reacted for about 2 hours to produce a vinyl ester resin (B1'-a) without a carboxyl group.

[0292] The reaction product containing the vinyl ester resin (B1'-a) was cooled to 90 °C, and 0.13 g of hydroquinone (0.003 parts by mass relative to 100 parts by mass in total of all compounding components) as a polymerization inhibitor was added, and 1546 g of styrene as a reactive diluent (monomer (C) containing an ethylenically unsaturated group) was added to obtain a mixture containing 54% by mass of vinyl ester resin and 46% by mass of styrene based on the total mass of the compounding components.

[0293] The compounding amounts of the respective components are shown in Table 2.

[0294] <Comparative Synthesis Example B1'-b>

[0295] In a 5 L four-necked detachable flask equipped with a stirrer, a reflux cooling tube, a gas inlet tube, and a thermometer, 1803 g of an epoxide (2) and 361 g of bisphenol A (the total amount of hydroxyl groups of bisphenol A was 33 moles relative to 100 moles of the total amount of the epoxide (b1-1)) were added and heated to 80°C. Then, 4.3 g of triethylamine as a catalyst (0.2 part by mass relative to 100 parts by mass in total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)) was added, and it was heated to 145°C and reacted for 1 hour to obtain a resin precursor (Q-4). Then, after cooling to 110°C, 505 g of styrene as a reactive diluent (10% by mass based on the total mass of the blended components), 0.05 g of 5% copper naphthenate as a polymerization inhibitor (0.0019 part by mass relative to 100 parts by mass in total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), 0.27 g of methylhydroquinone (0.01 part by mass relative to 100 parts by mass in total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), 1.5 g of trimethylhydroquinone (0.057 part by mass relative to 100 parts by mass in total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)), and 5.3 g of 2,4,6-tris(dimethylaminomethyl)phenol as an esterification catalyst (0.2 part by mass relative to 100 parts by mass in total of the epoxide (b1-1), bisphenol (b1-2), and unsaturated monocarboxylic acid (b1-3)) were added. After heating to 110°C, 454 g of methacrylic acid as an unsaturated monocarboxylic acid (b1-3) (the total amount of acid groups of methacrylic acid was 55 moles relative to 100 moles of the total amount of epoxy groups of the epoxide (b1-1)) was added dropwise over about 30 minutes, and then it was reacted for about 2 hours to synthesize a resin precursor (Q-5). Then, 33 g of fumaric acid (the acid groups of fumaric acid were 6 moles relative to 100 moles of the total amount of epoxy groups of the epoxide (b1-1)) was added and reacted for about 1 hour to obtain a vinyl ester resin (B1’-b) without a carboxyl group.

[0296] The reaction product containing the vinyl ester resin (B1’-b) was cooled to 90°C, and 1766 g of styrene as a reactive diluent (monomer (C) containing an ethylenically unsaturated group) was added to obtain a mixture containing 54% by mass of the vinyl ester resin and 46% by mass of styrene based on the total mass of the blended components.

[0297] The blending amounts of the respective components are shown in Table 2.

[0298] <Comparative Synthesis Example B1’-c>

[0299] Except for the blending composition shown in Table 2, synthesis was carried out in the same manner as in Synthesis Example B1’-b to obtain a vinyl ester resin (B1’-c) without a carboxyl group.

[0300] The reaction product containing the vinyl ester resin (B1’-c) was cooled to 90 °C, and 1830 g of styrene as a reactive diluent (monomer (C) containing an ethylenically unsaturated group) was added to obtain a mixture containing 54% by mass of the vinyl ester resin and 46% by mass of styrene based on the total mass of the blending components.

[0301] The blending amounts of the respective components are shown in Table 2.

[0302] <Comparative Synthesis Example B1’-d>

[0303] In a 5 L four-necked detachable flask equipped with a stirrer, a reflux condenser, a gas inlet tube, and a thermometer, 2220 g of an epoxy compound (2), 1.3 g of methylhydroquinone as a polymerization inhibitor (0.04 part by mass based on 100 parts by mass in total of the epoxy compound (b1-1) and the unsaturated monocarboxylic acid (b1-3)), and 9.7 g of tetradecyldimethylbenzylammonium chloride as an esterification catalyst (0.3 part by mass based on 100 parts by mass in total of the epoxy compound (b1-1) and the unsaturated monocarboxylic acid (b1-3)) were added and heated to 110 °C. Further, 1015 g of methacrylic acid as the unsaturated monocarboxylic acid (b1-3) (the acid group of methacrylic acid was 100 moles with respect to the total amount of 100 moles of the epoxy groups of the epoxy compound (b1-1)) was added dropwise over about 30 minutes, and then heated to 120 °C and reacted for about 3 hours to produce a vinyl ester resin (B1’-d) without a carboxyl group.

[0304] The reaction product containing the vinyl ester resin (B1’-d) was cooled to 90 °C, and 1750 g of phenoxyethyl methacrylate as a reactive diluent (monomer (C) containing an ethylenically unsaturated group) was added to obtain a mixture containing 65% by mass of the vinyl ester resin and 35% by mass of phenoxyethyl methacrylate based on the total mass of the blending components.

[0305] The blending amounts of the respective components are shown in Table 2.

[0306] <Comparative Synthesis Example B1’-e>

[0307] Except for the blending composition shown in Table 2, synthesis was carried out in the same manner as in Comparative Synthesis Example B1’-d to obtain a vinyl ester resin (B1’-e).

[0308] The blending amounts of the respective components are shown in Table 2.

[0309] <Synthesis Example B2-a>

[0310] In a 3 L four-necked detachable flask equipped with a thermometer, a stirrer, an inert gas inlet tube, and a reflux condenser, 330 g (30 mol) of ethylene glycol as the diol (b2-1), 876 g (65 mol) of propylene glycol, 119 g (5 mol) of dipropylene glycol, 695 g (40 mol) of maleic anhydride as the polybasic acid (b2-2-2) containing an ethylenically unsaturated group, and 1574 g (60 mol) of phthalic anhydride as the polybasic acid (b2-2-1) not containing an ethylenically unsaturated group were added, and a condensation reaction was carried out at 215 °C for 10 hours to obtain an unsaturated polyester resin (B2-a) as the unsaturated polyester resin (B2).

[0311] The reaction product containing the unsaturated polyester resin (B2-a) was cooled to 90 °C, and 1725 g of styrene as the reactive diluent (monomer (C) containing an ethylenically unsaturated group) was added to obtain a mixture containing 65% by mass of the unsaturated polyester resin and 35% by mass of styrene based on the total mass of the blended components.

[0312] The blending amounts of the respective components are shown in Table 3.

[0313] Table 1

[0314]

[0315] *1: Represented by assuming the total amount of epoxy groups of the epoxy compound (a1-1) to be 100 mol.

[0316] *2: Total amount of acid groups of methacrylic acid relative to 100 mol of the total amount of epoxy groups of the epoxy compound (a1-1)

[0317] *3: Total amount of acid groups derived from maleic anhydride relative to 100 mol of the total amount of epoxy groups of the epoxy compound (a1-1)

[0318]

[0319] Table 3

[0320]

[0321] [Determination and evaluation of vinyl ester resin and resin containing ethylenically unsaturated group]

[0322] Regarding the vinyl ester resin and the resin containing an ethylenically unsaturated group obtained in the above synthesis example, the following items were determined and evaluated. Their determination and evaluation results are shown in Tables 1 to 3.

[0323] It should be noted that, regarding the measurement sample used for the determination of acid value and hydroxyl value, a mixture containing the resin produced in the synthesis example and a reactive diluent (monomer (C) containing an ethylenically unsaturated group) was used. The details of this mixture are shown in Table 4.

[0324] Table 4

[0325]

[0326] <Acid value>

[0327] According to JIS K6901:2008 "Partial acid value (indicator titration method)", in an "Auto burette UCB-2000" (manufactured by Hiranuma Sangyo Co., Ltd.), using a mixed indicator of bromothymol blue and phenol red, the acid value was obtained by measuring the mass of potassium hydroxide required for neutralizing the acid components in the measurement sample.

[0328] <Hydroxyl value>

[0329] For the hydroxyl value of vinyl ester resin and resin containing an ethylenically unsaturated group, according to JIS K6901:2008 "Hydroxyl value (neutralization titration method)", the mass of potassium hydroxide required for neutralizing the acetic acid generated by the acetylation of 1 g of vinyl ester resin was measured, and the hydroxyl value was obtained.

[0330] It should be noted that the neutralization titration was carried out manually, and 1% phenolphthalein (ethanol solution) was used as the indicator.

[0331] <Weight-average molecular weight Mw, number-average molecular weight Mn and molecular weight distribution Mw / Mn>

[0332] The weight-average molecular weight Mw and number-average molecular weight Mn of vinyl ester resin and resin containing an ethylenically unsaturated group were measured by gel permeation chromatography (GPC) under the following measurement conditions and obtained as the molecular weight in terms of standard polystyrene conversion. The molecular weight distribution Mw / Mn was calculated from the values of number-average molecular weight Mn and weight-average molecular weight Mw.

[0333] 〔Measurement conditions〕

[0334] · Apparatus: High performance liquid chromatograph "Prominence (registered trademark)" (manufactured by Shimadzu Corporation)

[0335] · Column: "Shodex (registered trademark) LF-804" (manufactured by Resonac Co., Ltd.)

[0336] · Detector: Differential refractometer "Shodex (registered trademark) RI-71S" (manufactured by Resonac Co., Ltd.)

[0337] · Column temperature: 40 °C

[0338] · Sample: 0.2 mass% tetrahydrofuran solution of vinyl ester resin or unsaturated polyester resin

[0339] · Developing solvent: tetrahydrofuran

[0340] · Flow rate: 1.0 mL / minute

[0341] [Manufacture of resin composition]

[0342] Using each vinyl ester resin and the resin containing an ethylenically unsaturated group obtained in the above synthesis examples, a resin composition was manufactured.

[0343] Details of the compounds used in the following Examples and Comparative Examples are shown below.

[0344] (Monomer (C) containing an ethylenically unsaturated group)

[0345] · Bisphenol A dimethacrylate EO adduct: "NK Ester BPE-100", manufactured by Shin-Nakamura Chemical Co., Ltd.

[0346] (Compound (D))

[0347] · Magnesium oxide: "Magmicron MD-4AM-2", manufactured by Mikuni Shikiso Co., Ltd., magnesium oxide content 30 mass% (estimated)

[0348] (Thixotropic agent)

[0349] · Hydrophobic silica; "Reolosil PM-20L", manufactured by Tokuyama Corporation

[0350] <Example 1>

[0351] The vinyl ester resin (A1-a) as the vinyl ester resin (A) was 26.2 parts by mass, the unsaturated polyester resin (B2-a) as the resin (B) containing an ethylenically unsaturated group was 10.8 parts by mass, the vinyl ester resin (B1’-e) as the resin (B’) containing an ethylenically unsaturated group was 4.5 parts by mass, benzyl methacrylate as the monomer (C) containing an ethylenically unsaturated group was 25.3 parts by mass, ethylene glycol dimethacrylate was 10.5 parts by mass, an EO adduct of bisphenol A dimethacrylate was 15.7 parts by mass, and styrene was 5.7 parts by mass. After mixing in such a manner, 0.2 part by mass of water as the compound (E), 0.07 part by mass of 2,2-dimethoxy-2-phenylacetophenone as the photopolymerization initiator (F), 0.12 part by mass of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 0.8 part by mass of a thixotropic agent were added to the mixture, and it was mixed at 2000 to 3000 rpm for 20 minutes using a disperser (high-speed disperser “Homodisper 2.5 type” manufactured by Primix Corporation). 2 parts by mass of magnesium oxide (Magmicron MD-4AM-2) as the compound (D) was added thereto, and it was further mixed for about 1 minute to prepare a resin composition (X-1).

[0352] <Examples 2 to 8 and Comparative Examples 1 to 4>

[0353] Except for setting the raw materials and mixing ratios as described in Table 7, the same procedures as in Example 1 were carried out to prepare resin compositions (X-2) to (X-8) and (X’-1) to (X’-4).

[0354] [Measurement and Evaluation of Resin Compositions]

[0355] Regarding the resin compositions (X-1) to (X-8) and (X’-1) to (X’-4) obtained in the above Examples and Comparative Examples, the water content, viscosity, draw at the time of peeling, resistance feeling at the time of peeling, ball tack test, thickening property, and adhesiveness were measured and evaluated. Table 8 shows the results of their measurement and evaluation.

[0356] <Water Content (Water Content in the Resin Composition Excluding Compound (D))>

[0357] In the production of the above resin composition, 1.5 g of a resin composition (excluding compound (D)) obtained by mixing the vinyl ester resin (A), the resin (B) containing an ethylenically unsaturated group, the monomer (C) containing an ethylenically unsaturated group, the compound (E), and the photopolymerization initiator (F) was collected, and the water content in the resin composition excluding compound (D) was measured by volumetric titration using a Karl Fischer moisture meter as follows.

[0358] · Apparatus: "701KF Titrino" (manufactured by Metrohm Japan Co., Ltd.)

[0359] · Karl Fischer reagent: "Aquamicron (registered trademark) Titrant SS 3mg" (manufactured by Mitsubishi Chemical Corporation)

[0360] · Dehydrating solvent: chloroform / methanol = 3 vol% / 1 vol%

[0361] <Viscosity>

[0362] After preparing the resin compositions (X-1) to (X-8) and (X'-1) to (X'-4), 280 g was added to a 300-ml container immediately for each, and they were stored in a sealed state at normal humidity (relative humidity 50 - 60%) at 25°C. Then, the viscosities at 25°C of the stored resin compositions (X-1) to (X-8) and (X'-1) to (X'-4) were measured 1 hour, 2 days, and 5 days after the preparation of the resin compositions.

[0363] Note that for viscosity measurement, when the viscosity exceeds 0 Pa·s and is 100.0 Pa·s or less, an "RB80 viscometer" (manufactured by Toki Sangyo Co., Ltd.; rotor No. 3 - 4) was used, and when the viscosity exceeds 100.0 Pa·s, an "HBDVE viscometer" (manufactured by Eihong Seiki Co., Ltd.; T-bar spindle T-A - T-D, rotation speed: 1 rpm) was used.

[0364] The rotors and rotation speeds corresponding to the measured viscosities are shown in Table 5, and the use of T-bar spindles is shown in Table 6.

[0365] Table 5

[0366] Viscosity [Pa·s] Rotor No. Rotation speed [rpm] Greater than 0 and less than or equal to 1.0 3 60 Greater than 1.0 and less than or equal to 5.0 4 60 Greater than 5.0 and less than or equal to 25.0 4 12 Greater than 25.0 and less than or equal to 50.0 4 6 Greater than 50.0 and less than or equal to 100.0 4 3

[0367] Table 6

[0368] Viscosity [Pa·s] T-shaped rotor Greater than 100 and less than or equal to 800 T-A Greater than 800 and less than or equal to 1600 T-B Greater than 1600 T-C

[0369] The viscosities of the resin compositions (X-1) to (X-8) and (X'-1) to (X'-4) were evaluated according to the following criteria.

[0370] · 1 hour after the preparation of the resin composition

[0371] A: Viscosity is 0.1 - 3.0 Pa·s

[0372] B: Viscosity is less than 0.1 Pa·s or exceeds 3.0 Pa·s

[0373] · Two days after the resin composition is prepared

[0374] A: The viscosity is 30 to 1,500 Pa·s

[0375] B: The viscosity is less than 30 Pa·s or exceeds 1,500 Pa·s

[0376] · Five days after the resin composition is prepared

[0377] A: The viscosity is 400 to 3,500 Pa·s

[0378] B: The viscosity is less than 400 Pa·s or exceeds 3,500 Pa·s

[0379] <Thickening property>

[0380] The thickening property of the resin composition was evaluated according to the following evaluation criteria.

[0381] A: The viscosities of the resin composition two days after the resin composition is prepared and five days after the resin composition is prepared are evaluated as A (good thickening property).

[0382] B: At least one of the evaluations of the viscosities of the resin composition two days after the resin composition is prepared and five days after the resin composition is prepared is B (poor thickening property).

[0383] <Drawing during peeling>

[0384] Two pieces of roving cloth (“WR 570C-100”, manufactured by Nitto Boseki Co., Ltd.) were cut into 100 mm × 200 mm, and the two pieces were overlapped. About 45 g of the resin composition was impregnated using a degassing roller to obtain a laminate (glass content: about 40% by mass). The laminate was sandwiched between polyethylene terephthalate films cut into 250 mm × 250 mm to obtain a laminate for evaluation. The laminate for evaluation was allowed to stand at room temperature and normal humidity (in the dark, relative humidity 50 to 60%). Two days or seven days after the resin composition was prepared, the layers of the laminate for evaluation were peeled by hand, and the presence or absence of drawing was visually evaluated according to the following evaluation criteria.

[0385] A: There is drawing

[0386] B: There is no drawing

[0387] <Resistance feeling during peeling>

[0388] Two pieces of roving fabric (“WR 570C-100”, manufactured by Nitto Boseki Co., Ltd.) were cut out to 100 mm × 200 mm, the two pieces were overlapped, and about 45 g of a resin composition was impregnated using a degassing roller to obtain a laminate (glass content of about 40% by mass). The laminate was sandwiched between polyethylene terephthalate films cut out to 250 mm × 250 mm to obtain a laminate for evaluation. The laminate for evaluation was allowed to stand at room temperature and normal humidity (in the dark, relative humidity 50 - 60%), and after 2 days or 7 days after the resin composition was prepared, the layers of the laminate for evaluation were peeled by hand, and the presence or absence of a resistance feeling was evaluated according to the following evaluation criteria.

[0389] A: There is a resistance feeling

[0390] B: Slightly has a resistance feeling

[0391] C: There is no resistance feeling

[0392] Note that “having a resistance feeling” means that force is required for peeling.

[0393] <Ball tack test>

[0394] Two pieces of glass cloth (“WF 350 100BS6”, manufactured by Nitto Boseki Co., Ltd.) were cut out to 100 mm × 200 mm, the two pieces were overlapped, and about 20 g of a resin composition was impregnated using a degassing roller to obtain a laminate (glass content of about 40%). Note that the laminate was produced in such a way that it had a resin composition non-impregnated portion of 100 mm × 100 mm, a resin composition impregnated portion of 100 mm × 100 mm, and a thickness of 0.6 mm. The laminate was sandwiched between polyethylene terephthalate films cut out to 250 mm × 250 mm and placed on a glass plate to obtain a laminate for evaluation. The laminate for evaluation was allowed to stand at 23°C ± 3°C and normal humidity (in the dark, relative humidity 50 - 60%). Then, after 2 days or 7 days after the resin composition was prepared, the layers of the glass cloth of the laminate for evaluation were peeled, and the peeled surface was used as the adhesive portion (resin composition impregnated portion) of the adhesive sheet, and an inclined ball tack test (30° inclination) was carried out with reference to “14 Inclined ball tack” of JIS Z 0237:2022 (Test methods for adhesive tapes and adhesive sheets). Specifically, as Figure 1As shown, a ball rolling device using one of the evaluation laminates with the interlayer of the glass cloth peeled off and provided on a base inclined at 30° was tested in accordance with the "14.3 Test Method" of JIS Z0237:2022 (Test Methods for Adhesive Tapes and Adhesive Sheets). It should be noted that the resin composition non-impregnated part of one of the evaluation laminates with the interlayer of the glass cloth peeled off was set as the approach runway (100 mm) in the inclined ball tack test, and the resin composition impregnated part was set as the measurement part (100 mm).

[0395] According to the results of the inclined ball tack test (30° inclination), Table 8 shows the maximum ball number at which the ball stops in 5 seconds in the adhesion part (resin composition impregnated part) (Measurement 1), and the maximum ball number at which the ball rotates less than one turn during 5 seconds in the adhesion part (Measurement 2).

[0396] <Adhesiveness>

[0397] According to the results of the inclined ball tack test, the adhesiveness was evaluated according to the following evaluation criteria.

[0398] A: Meets the following requirements 1 and 2

[0399] B: Does not meet at least one of the following requirements 1 and 2

[0400] Requirement 1: The maximum ball number at which the ball stops in 5 seconds in the adhesion part (Measurement 1) is 5 or more

[0401] Requirement 2: The maximum ball number at which the ball rotates less than one turn during 5 seconds in the adhesion part (Measurement 2) is 7 or more

[0402]

[0403]

[0404] It was confirmed that the resin composition containing vinyl ester resin (A), resin (B) containing an olefinically unsaturated group, monomer (C) containing an olefinically unsaturated group, compound (D), and compound (E) thickened at an appropriate rate over time at room temperature and had adhesiveness after thickening.

Claims

1. A resin composition comprising: Vinyl ester resin A, Resin B containing ethylenically unsaturated groups, Monomer C containing ethylenically unsaturated groups, a compound D of at least one selected from oxides of Group 2 elements and hydroxides of Group 2 elements, and a compound E selected from at least one of water and a compound containing a hydroxyl group, The vinyl ester resin A has a weight average molecular weight Mw of 6,000 or more, and a ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn of 2.0 or more, The ethylenically unsaturated group-containing resin B is at least one selected from a vinyl ester resin B1 having a carboxyl group and a weight average molecular weight Mw of less than 6,000, and an unsaturated polyester resin B2 having a carboxyl group and a weight average molecular weight Mw of less than 6,000.

2. The resin composition according to claim 1, comprising 50 to 70% by mass of the vinyl ester resin A and 30 to 50% by mass of the resin B containing an ethylenically unsaturated group, based on 100% by mass of the total of the vinyl ester resin A and the resin B containing an ethylenically unsaturated group. 3 . The resin composition according to claim 1 , wherein the weight average molecular weight (Mw) of the vinyl ester resin (A) is 35,000 or less. The resin composition according to claim 1 or 2, wherein the weight average molecular weight Mw of the vinyl ester resin A is 15,000 or less. 5 . The resin composition according to claim 1 , wherein the weight average molecular weight Mw of the vinyl ester resin B1 is 2,000 or more. 6 . The resin composition according to claim 1 , wherein the vinyl ester resin B1 has a weight average molecular weight Mw of 3,000 to 5,000. 7 . The resin composition according to claim 1 , wherein the unsaturated polyester resin B2 has a weight average molecular weight Mw of 1,000 to 10,000.

8. The resin composition according to claim 1 or 2, wherein the vinyl ester resin A is a vinyl ester resin A1 which is an addition reaction product of a resin precursor P1 and a polybasic acid anhydride a-4, wherein the resin precursor P1 is a reaction product of an epoxy compound a-1 having two epoxy groups in one molecule, an unsaturated monobasic acid a-2, and a polybasic acid anhydride a-3, The total amount of the acid groups reactive with the epoxy groups derived from the polybasic acid anhydride a-3 is 5 to 25 mol, based on 100 mol of the total amount of the epoxy groups of the epoxy compound a-1.

9. The resin composition according to claim 1 or 2, wherein the vinyl ester resin B1 is a vinyl ester resin B1-1 which is a reaction product of a resin precursor Q2 and an unsaturated polybasic acid b1-4, the resin precursor Q2 is a reaction product of a resin precursor Q1 and an unsaturated monobasic acid b1-3, and the resin precursor Q1 is a reaction product of an epoxy compound b1-1 having two epoxy groups in one molecule and a bisphenol compound b1-2.

10. The resin composition according to claim 1 or 2, wherein the unsaturated polyester resin B2 is a reaction product of a diol b2-1 and a polyacid b2-2. The polyacid b2-2 includes a polyacid b2-2-1 containing an ethylenically unsaturated group and a polyacid b2-2-2 not containing an ethylenically unsaturated group. 11 . The resin composition according to claim 1 , wherein the Mw / Mn of the vinyl ester resin A is 3.0 or more, and an acid value is 20 KOHmg / g or more. 12 . The resin composition according to claim 1 , wherein the acid value of the resin B containing an ethylenically unsaturated group is 20 KOHmg / g or more. 13 . The resin composition according to claim 1 , wherein the resin B containing an ethylenically unsaturated group is only the vinyl ester resin B1. 14 . The resin composition according to claim 1 , wherein the resin B containing an ethylenically unsaturated group comprises the vinyl ester resin B1 and the unsaturated polyester resin B2. 15 . The resin composition according to claim 14 , wherein the mass ratio of the vinyl ester resin B1 to the unsaturated polyester resin B2, that is, the vinyl ester resin B1 / the unsaturated polyester resin B2 is 40 / 60 to 80 / 20. 16 . The resin composition according to claim 1 , wherein the unsaturated group of the monomer C containing an ethylenically unsaturated group is at least one selected from the group consisting of a vinyl group (including an allyl group) and a (meth)acryloyl group.

17. The resin composition according to claim 1 or 2, wherein the monomer C containing an ethylenically unsaturated group is at least one selected from the group consisting of styrene, vinyltoluene, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate and ethoxylated bisphenol A di(meth)acrylate. 18 . The resin composition according to claim 1 , wherein the compound D is at least one selected from the group consisting of magnesium oxide, magnesium hydroxide, calcium oxide and calcium hydroxide.

19. A composite material comprising the resin composition according to claim 1 or 2, and a fiber substrate G.

20. A lining member comprising the fiber base material G.

Citation Information

Patent Citations

  • Repairing method for existing pipe and repairing system for existing pipe

    JP2020082408A